Bottom-up, scalable synthesis of oxide-based sub-nano and nanofilaments, nanofilament-based 2D flakes and mesoporous powders

JP2024507122A5Pending Publication Date: 2025-02-19DREXEL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023548178
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-11-04
Filing Date
2022-02-11
Publication Date
2025-02-19

AI Technical Summary

Technical Problem

There is a need for stable one-dimensional (1D) and two-dimensional (2D) metal oxide nanomaterials, particularly those that can be synthesized in bulk from non-layered solids and are stable in water, as existing methods are limited to layered solids and 1D nanofilaments are not water-stable.

Method used

A bottom-up approach is used to synthesize 10 types of binary and ternary titanium carbides, nitrides, borides, phosphides, and silicides at near-room temperatures, converting them into 2D flakes using tetramethylammonium hydroxide (TMAH) solution, resulting in nanofilaments and mesoporous powders with specific structural and chemical properties.

Benefits of technology

The synthesized materials exhibit good performance in lithium-ion and lithium-sulfur systems, show potential for biomedical applications by reducing cancer cell viability, and provide a scalable, cost-effective method for producing 2D materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000037_0000
    Figure 00000037_0000
  • Figure 00000037_0001
    Figure 00000037_0001
  • Figure 00000037_0002
    Figure 00000037_0002
Patent Text Reader

Abstract

Provided is a method for converting binary and ternary titanium carbides, nitrides, borides, phosphides, aluminides, and silicides, by a bottom-up approach, into nanofilaments that in some cases self-assemble into 2D flakes by immersion in a quaternary ammonium solution at moderate temperatures. The resulting flakes are C-containing anatase-based layers whose cross-sections consist of nanofilaments, some of which in some cases are several microns long. Electrodes made from these materials have performed well in energy systems. The materials also reduce the viability of some cancer cells. Also provided are mesoporous materials, devices, and related methods.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Related Applications This application claims priority to and the benefit of U.S. Patent Application No. 63 / 148,348, filed February 11, 2021, U.S. Patent Application No. 63 / 167,197, filed March 29, 2021, U.S. Patent Application No. 63 / 171,293, filed April 6, 2021, and U.S. Patent Application No. 63 / 275,631, filed November 4, 2021. The foregoing applications are hereby incorporated in their entireties for all purposes.

[0002] Technical Field The present disclosure relates to the field of 1D and 2D materials, and to the field of metal oxide-based nanomaterials. [Background technology]

[0003] One-dimensional (1D) and two-dimensional (2D) materials have advantages over their 3D counterparts. Historically, the starting point for the synthesis of 2D materials in bulk has mostly been layered solids such as clays, graphite, or more recently MAX phases. The idea of ​​synthesizing 2D solids in bulk from non-layered solids has been considered difficult / impossible. Thus, there is a need for 2D solids, especially such solids synthesized in bulk from non-layered solids. Most 1D nanofilaments are not stable in water. Thus, there is a need for 1D solids, especially solids that are stable in water. Summary of the Invention

[0004] As an example of the disclosed technology, we have used a bottom-up approach to convert ten binary and ternary titanium carbides, nitrides, borides, phosphides, and silicides into 2D flakes, e.g., by immersion in tetramethylammonium hydroxide (TMAH) solutions at temperatures ranging from 25 to 85 °C. Based on X-ray diffraction, density functional theory, X-ray photoelectron, electron energy loss, Raman, X-ray absorption near-edge structure spectroscopy, transmission and scanning electron microscope images, and selected area diffraction, the resulting flakes are C-containing anatase-based layers with cross-sections (in some embodiments) of ≈6x10 Å. 2 They concluded that the films consist of nanofilaments, some of which are several microns long. Electrodes made from some of these films have shown good performance in lithium-ion and lithium-sulfur systems. These materials also reduce the viability of cancer cells, showing potential for biomedical applications. Non-layered, inexpensive precursors (e.g. TiC, TiB 2 The synthesis of two-dimensional (2D) materials consisting of 1D bodies using SiC, TiN, etc. at near-room temperature is a paradigm shift that promises to open up new and exciting avenues of research and applications.

[0005] To meet the stated long-standing needs, the present disclosure provides compositions that include a plurality of metal oxide (e.g., metal oxide-based) nanofilaments and / or sub-nanofilaments, and optionally an amount of carbon. (As described herein, the nanofilaments can include titanium.) Examples of such compositions are found in "Bottom-up, scalable synthesis of anatase nanofilament-based two-dimensional titanium carbo-oxide flakes", Badr et al., Materials Today (2021), the entirety of which is incorporated herein by reference for all purposes.

[0006] Also provided is a device, the device comprising a composition according to the present disclosure, for example, a composition according to any one of embodiments 1-16.

[0007] Further disclosed is a method that includes operating a device according to the present disclosure, such as a device according to embodiment 16.

[0008] Also disclosed is a method comprising contacting a mono-, binary, ternary or more carbide, nitride, boride, phosphide, aluminide, or silicide, or titanium metal, with a quaternary ammonium salt and / or a base, wherein the mono-, binary, ternary or more carbide, nitride, boride, phosphide, aluminide, or silicide, or titanium metal, is optionally water insoluble, and the water insoluble binary, ternary or more carbide, nitride, boride, phosphide, aluminide, or silicide optionally comprises a transition metal, and the transition metal optionally comprises titanium, and wherein the contacting is performed under conditions sufficient to produce a nanofilamentary product.

[0009] In addition, particulate TiO 2 with a quaternary ammonium salt, said contacting step being carried out under conditions sufficient to produce an anatase nanoparticle product, optionally wherein at least some of the nanoparticles have a diameter of from about 2 nm to about 1000 nm, optionally from about 10 nm to about 100 nm.

[0010] Further provided in accordance with the present disclosure is a composition comprising a population of anatase nanoparticles, eg, produced in accordance with one of embodiments 38-42.

[0011] In addition, TiO 2 with a population of anatase nanoparticles produced in accordance with the present disclosure, eg, according to any one of embodiments 38-42.

[0012] Also disclosed is a method that includes contacting a mono-, binary, ternary or more carbide, nitride, boride, phosphide, aluminide, or silicide, or titanium metal with a quaternary ammonium salt and / or a base, wherein the mono-, binary, ternary or more carbide, nitride, boride, phosphide, aluminide, or silicide, or titanium metal is optionally water insoluble, and the water insoluble binary, ternary or more carbide, nitride, boride, phosphide, aluminide, or silicide optionally comprises a transition metal, and the transition metal optionally comprises titanium, the contacting step is optionally performed with shaking, and the contacting step is performed under conditions sufficient to produce mesoporous particles.

[0013] Also disclosed is a method comprising the step of contacting a mono-, binary, ternary or more carbide, nitride, boride, phosphide, aluminide, or silicide, or titanium metal, with a quaternary ammonium salt and / or a base, wherein the mono-, binary, ternary or more carbide, nitride, boride, phosphide, aluminide, or silicide, or titanium metal, is optionally water insoluble, the water insoluble binary, ternary or more carbide, nitride, boride, phosphide, aluminide, or silicide optionally comprises a transition metal, the transition metal optionally comprises titanium, the contacting step is optionally performed with shaking, and the contacting step is followed by washing with at least one salt and is performed under conditions sufficient to produce mesoporous particles.

[0014] Further disclosed is a method comprising the step of contacting a mono-, binary, ternary or higher carbide, nitride, boride, phosphide, aluminide, or silicide, or titanium metal, with a quaternary ammonium salt and / or a base, wherein the mono-, binary, ternary or higher carbide, nitride, boride, phosphide, aluminide, or silicide, or titanium metal, is optionally water insoluble, and the water insoluble binary, ternary or higher carbide, nitride, boride, phosphide, aluminide, or silicide optionally comprises a transition metal, which transition metal optionally comprises titanium, and wherein the contacting is performed at a temperature of about 50 to about 95° C., optionally with shaking, followed by washing with LiCl to produce mesoporous particles.

[0015] Also provided in accordance with the present disclosure are mesoporous particles, eg, produced in accordance with any one of embodiments 45-47.

[0016] Further provided is a composition comprising mesoporous particles, said mesoporous particles comprising titanium, said mesoporous particles exhibiting an XRD pattern exhibiting reduced (104) and (105) peaks at about 38° and about 55° two-theta (2θ) compared to the XRD pattern of nano or bulk anatase.

[0017] Also provided is a method comprising delivering a therapeutic agent to a subject, the therapeutic agent being contained in a composition according to the present disclosure, e.g., according to any one of aspects 48-49.

[0018] Also disclosed is a method comprising delivering a therapeutic agent to a subject, the therapeutic agent being contained in a composition according to the present disclosure, e.g., according to any one of aspects 48-49.

[0019] Additionally, an electrode is provided, said electrode comprising a composition according to the present disclosure, for example according to any one of aspects 48-49.

[0020] Also disclosed is a device, the device comprising a composition according to the present disclosure, eg, according to any one of aspects 48-49.

[0021] Also provided is a method, the method comprising operating an apparatus according to the present disclosure, for example according to any one of aspects 52-53. [Brief description of the drawings]

[0022] The patent or application file contains at least one color drawing / photograph. Copies of this patent or patent application publication with color drawing(s) / photograph(s) will be provided by the Office upon request and payment of the necessary fee.

[0023] In the drawings, which are not necessarily drawn to scale, like numerals may represent like components in different views. Like numerals with different letter suffixes may represent different instances of like components. The drawings illustrate generally, by way of example, but not by way of limitation, various aspects discussed in the present specification. In the drawings:

[0024] [Figure 1] Figures 1A-1D. Fabrication process, scanning electron microscope (SEM) micrographs, and density functional theory (DFT) structures. (Fig. 1A) Schematic of the fabrication process. (Fig. 1B) Typical cross-sectional SEM micrograph of TiC-derived filtration film (FF). Note the undigested TiC particle in the lower right corner. The inset shows a photo of a typical colloidal suspension. (Fig. 1C) Isometric side view of a four-Ti-layered 2D anatase-based structure with the TiO4C6 chemical structure that best fits the XRD and selected area diffraction (SAD) results. The blue, orange, red, and black spheres represent Ti, 2- and 3-coordinated O, and C, respectively. The vertical arrows on the left indicate approximate dimensions. (Fig. 1D) Top view of nanofilaments (nfs) growing in the

[0200] (top) and

[0110] (bottom) directions. The inset (Fig. 1D) compares the experimental LP (dashed line) with the DFT prediction (solid line) as a function of the number of Ti layers. Our coordinate system is shown in the bottom left of c and d and is not that of bulk anatase. [Diagram 2] Figure 2A-2D Characterization of 2D materials. (Figure 2A) Log-scale XRD pattern of filtered vertically aligned Ti3AlC2-derived film in transmission mode. The inset shows the pattern of the horizontally aligned film. The 5° 2θ peak is due to Kapton tape. The blue boxes are the 2θ positions determined from the TEM-SAD patterns (Table 3). (Figure 2B) Raman spectra of FF obtained from the indicated precursors. All powders were heated at 50 °C for 3 days and washed with ethanol and water, except for the top TiB2, which was treated at 80 °C for 2 days. All peaks belong to anatase.

[15] (Figure 2C) Core loss electron energy loss spectroscopy (EELS) data measured from five particles. The graph shows the carbon-K edge at ~280 eV energy loss, the titanium-L3,2 peak at ~450 eV energy loss, and the oxygen-K edge at ~530 eV energy loss. All spectra are normalized to the Ti edge peak intensity and vertically separated for clarity. (Figure 2D) XANES results for TiC-derived films combined with results for anatase, Ti3AlC2, TiC, and TiCl3. All TiC samples were reacted in TMAH at 50 °C for 3 days. The inset shows the derivative of the X-ray absorption near edge structure (XANES). [Diagram 3]Figures 3A-3D Morphology of titanium carbide (TCO) flakes. (Figure 3A) Typical transmission electron microscopy (TEM) image of a TCO flake with lateral size >4 μm. The top right inset shows the SAD of the area circled in red. The two arcs show fibrous structures along the

[0110] and

[0200] directions. The bottom inset is a high magnification of the top left corner showing frayed nanofilaments along the arcs. (Figure 3B) Scanning transmission electron microscopy (STEM) showing individual filaments with widths of ≈10 Å. The bottom inset shows nanofilaments chemically "pulled" from the large central Ti3AlC2 particle. (Figure 3C) Atomic force microscopy (AFM) of TiC-derived TCO self-assembled nanofilaments heated in TMAH at 80 °C for 3 days and washed with water. (Figure 3D) Same as (Figure 3C), but after diluting the colloidal suspension 500 times and drop-casting onto a glass slide. The inset shows the height profile corresponding to the blue line in (Figure 3D); the height of the thinnest filament is ≈1.5 nm. [Figure 4] Figures 4A-4D (Figure 4A) Tauc plots of films derived from various precursors. Dashed lines model the baseline by Urbach tail absorption; solid lines fit the linear part. Charge-discharge curves (Figure 4B) Voltage profile of Ti3AlC2-derived electrode material when tested in a lithium-ion battery (LIB) at 20 mA g-1. The inset shows the cyclic voltammogram at 0.1 mV s-1. (Figure 4C) Charge-discharge curves of the TCO cathode when tested in a lithium-sulfur (Li-S) battery at various current rates. (Figure 4D) Viability of cancer cells (see text). Values ​​represent mean ± SD (n = 3); *p < 0.05. [Diagram 5] Figure 5A-5F. SEM micrographs of cross sections of FFs fabricated starting from (Figure 5A) Ti3SiC2, (Figure 5B) Ti3AlC2, (Figure 5C) Ti2SbP, (Figure 5D) TiN, (Figure 5E) TiB2, and (Figure 5F) Ti5Si3 and after ethanol and LiCl washing. Insets show the corresponding colloidal suspensions and FFs. [Figure 6]Figure 6A-6C X-ray diffraction patterns (vertically shifted for clarity) of FFs (Figure 6A) from parent TiC, Ti3AlC2, and Ti3SiC2 precursors (black lines) and 2D TCO films derived from them after washing with ethanol and without sonication (red, blue, and green curves, respectively). (Figure 6B) TiC (red, bottom), Ti3AlC2 (blue, middle), and Ti3SiC2 (green, top) derived films after washing with ethanol and then with LiCl solution. (Figure 6C) TiB2 (red, bottom), TiN (blue, middle), and Ti5Si3 (green, top) derived films after washing with ethanol and then with LiCl solution. [Figure 7] Figure 7A-7B (Figure 7A) Setup used to obtain XRD patterns from vertically aligned films in transmission mode. The inset shows Kapton tape with drop-cast film taped to a vertical aluminum sample holder. (Figure 7B) XRD pattern of vertically aligned ethanol-washed FF derived from the indicated precursor (shifted vertically for clarity). The pattern of the Kapton tape is also shown. Asterisks indicate peaks belonging to unreacted precursor. Except for one case, the precursors were heated at 50 °C for 3 days in TMAH solution as described in the Materials and Methods section. In one case, TiC powder was immersed in TMAH at 50 °C for 11 days (blue, top). For XRD characterization, 1–1.5 ml of the colloidal suspension was drop-cast by pipette onto the Kapton tape and air-dried. The 5° vertical black lines originate from the Kapton tape. The blue lines are a guide to the anatase-based 2D structure. [Figure 8]Figures 8A-8F (Figure 8A) and (Figure 8B) Typical TEM images of TiC-derived flakes (50 °C, 3 days). (Figure 8C) Same as (Figure 8A), but TiC was heated at 80 °C for 3 days, highlighting the fibrous nature of the TCO flakes. (Figure 8D) Nanofilaments crystallizing from the amorphous TCO background. The inset shows a high-resolution image of crystalline nanofilaments, 2-3 nm wide and several microns long. In the previous case, the reaction products were washed with water. (Figure 8E) Ti3SiC2-derived flakes captured from a milled FF (50 °C for 3 days, washed with ethanol). (Figure 8F) Nanofilaments (dark particles in the center) that appear to be chemically "pulled" out of the Ti3AlC2 phase (50 °C for 3 days, washed with ethanol and water). The inset shows the SAD pattern of the area circled in red. The inset in f shows both faint rings (due to TCO) and MAX phase spots. [Figure 9] 9A-9B (FIG. 9A) TEM and (FIG. 9B) AFM micrographs of TiC-derived material (heated at 80° C. for 5 days and washed with water). AFM samples were spin-coated onto glass slides from the initial suspension after dilution. [Figure 10] Figures 10A-10B. (Figure 10A) Six-layer anatase structure. Slab thickness is ≈8 Å. (Figure 10B) Phonon density of states for the four-layer structure shown in Figure 1C. [Figure 11] Figure 11 XPS spectra after LiCl cleaning in the Ti 2p region (first column), C 1s region (second column), O 1s region (third column) and the Fermi edge (fourth column) obtained from TiC- (first row, top), Ti3AlC2- (second row), Ti3SiC2- (third row), TiN- (fourth row), TiB2- (fifth row), and TiO2-based (sixth row) films. Peak fits and results are summarized in Tables 4 and 7. The vertical dashed lines are guides for the eye. [Figure 12]Figures 12A-12B XPS spectra as a function of treatment in the Ti 2p region (first column), C 1s region (second column), O 1s region (third column), and Fermi edge (last column) for (Figure 12A) Ti3AlC2-based and (Figure 12B) Ti3SiC2-based filter films. The dashed vertical lines are guides for the eye. In particular, the position of the Ti peak seems unaffected in the case of Ti3AlC2 by the solutions used to wash the films, or even after heating to 800 °C in Ar (compare the spectrum above in blue with that below in a). [Figure 13] Figures 13A-13E XPS spectra in the (Figure 13A) N 1s and (Figure 13B) Cl 2p regions of TCO FFs derived from TiC (black, bottom), Ti3AlC2 (red, second from bottom), Ti3SiC2 (blue, third from bottom), TiN (green, third from top), TiB2 (purple, second from top), and TiO2 (yellow, top) powders, (Figure 13C) Si 2p spectrum of Ti3SiC2-derived FF, (Figure 13D) Al 2p spectrum of Ti3AlC2-derived FF, (Figure 13E) B 1s spectrum of TiB2-derived FF. All samples were washed with ethanol and LiCl before filtration and vacuum dried before XPS analysis. [Figure 14] 14A-14B (Fig. 14A) Thermogravimetric plots for all samples at 10 °C / min heating in Ar to 800 °C. The ethanol-labeled samples were washed with ethanol, and the LiCl-labeled samples were washed first with ethanol and then with LiCl solution. (Fig. 14B) Films from TiC heated to 800 °C in air. c) Mass spectrometry results of b. Up to ≈400 °C, most of the gas released is water. Above 400 °C, CO2 is released. The black dashed vertical lines are guides to the eye. [Figure 15] Figure 15. Rietveld refinement of the XRD diffractogram of the LiCl washed filtration membrane heated to 800 °C in Ar. The χ2 values ​​are shown in the figure. The results are summarized in Table 8. The purple line shows the difference between the fit in red and the experimental results in black. [Figure 16]Figures 16A-16B: (Figure 16A) XRD diffraction patterns of TiO2-derived materials heated in TMAH for the times and temperatures indicated. In 2D anatase, the (104) and (105) peaks are absent, and the 63° peak is shifted towards 60°. (Figure 16B) TEM of 20 nm anatase nanoparticles. The inset shows a high magnification image and SAD pattern of the resulting TiO2 nanoparticles. [Figure 17] 17A-17D Electrochemical performance of Ti3AlC2-based TCOs as electrode materials for lithium-ion batteries. (FIG. 17A) Electrochemical impedance spectroscopy Nyquist plots at open circuit potential, (FIG. 17B) specific capacity vs. cycle number and specific current. (FIG. 17C) Voltage profile at a specific current of 100 mA g-1. (FIG. 17D) Specific capacity and coulombic efficiency vs. cycle number for the cell shown in c. [Figure 18] FIG. 18A-18B Electrochemical characteristics of TiC-based FF electrodes in Li-S cells: (FIG. 18A) CV curves, (FIG. 18B) cycling stability at 0.2° C. with S loading of 0.8 mg. The capacity was more or less constant at ≈1000 mAh / g for about 300 cycles before fading. [Figure 19] FIG. 19 provides an image of an exemplary mesoscopic material according to the present disclosure. [Figure 20] Table 1 provides exemplary sources of powders and reagents used in this study. [Figure 21] Table 2 summarizes exemplary precursors, Ti:TMAH molar ratios, and synthesis conditions. [Figure 22] Table 3 summarizes the interlayer spacing (d) values ​​and corresponding diffraction angles (2θ) obtained from the XRD patterns shown in Fig. 2a, as well as a comparison with the values ​​obtained from seven different SAD patterns obtained from five different specimens. All samples derived from the parent TiC were heated to 50 °C and then washed with ethanol and water. [Diagram 23] Table 4 summarizes the fits of the XPS results shown in FIG. [Figure 24]Table 5 provides the chemical composition of five different flakes inferred from the EELS measurements shown in Figure 2c. The last row indicates the possible chemical reactions present, where X is a sum of O, C, and N. The flakes were prepared by dry rubbing a filter film made by heating TiC powder in TMAH at 50 °C for 3 days and then washed with ethanol. [Diagram 25] Table 6 shows the chemical composition of a number of flakes from different precursors, estimated from EDS measurements. The last row shows the possible Ti:O ratios of these samples. SEM-EDS measurements were taken from cross-sections of filter films made from precursor Ti3AlC2, Ti3SiC2, Ti3GaC2 powders reacted with TMAH for 72 h at 50 °C and washed with ethanol and then with LiCl solution. TEM-EDS measurements were performed on samples prepared by dry rubbing filter films from Ti3SiC2 and TiB2 made by reacting the powders with TMAH for 72 h at 50 °C and washing with ethanol. [Figure 26] Table 7 provides the Ti:O chemistry obtained from the Ti region under the ≈459 eV peak and the O region under the ≈530 eV peak shown in FIG. [Figure 27] Table 8 summarizes the Rietveld analysis of the filtration films after heating to 800° C. in Ar. The corresponding XRD patterns are plotted in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] The present disclosure may be understood more readily by reference to the following detailed description of the preferred embodiments and the examples included therein.

[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art. In case of conflict, the present specification, including definitions, shall prevail. Preferred methods and materials are described below, but methods and materials similar or equivalent to those described herein may be used in the practice or testing. All publications, patent applications, patents and other documents described herein are incorporated by reference in their entirety. The materials, methods and examples disclosed herein are illustrative only and are not intended to be limiting.

[0027] The singular forms "a," "an," and "the" include plural references unless the context clearly indicates otherwise.

[0028] As used in the specification and claims, the term "comprising" can include the embodiments "consisting of" and "consisting essentially of." As used herein, the terms "comprise(s)," "include(s)," "having," "has," "can," "contain(s)," and variations thereof are intended to be open-ended transitional phrases, terms, or words that require the presence of the named components / steps and permit the presence of other components / steps. However, such descriptions should be construed as also describing the composition or process as "consisting of" and "consisting essentially of" the recited components / steps, which permits the recited components / steps along with impurities that may result therefrom and excludes other components / steps.

[0029] As used herein, the terms "about" and "at or about" mean that the quantity or value in question may be approximately or approximately the same as the other value specified. As used herein, it is generally understood to be a nominal value, indicated with a variation of ±10%, unless otherwise indicated or inferred. The term is intended to convey that similar values ​​promote the same results or effects as described in the claims. That is, it is understood that the amounts, sizes, formulations, parameters, and other quantities and characteristics are not and need not be precise, but can be approximated and / or larger or smaller as desired, reflecting tolerances, conversion factors, rounding, measurement errors, etc., and other factors known to those skilled in the art. In general, the amount, size, formulation, parameter, or other quantity or characteristic is "about" or "approximate", whether or not it is expressly stated as such. When "about" is used before a quantitative value, it is understood that the parameter also includes the specific quantitative value itself, unless specifically stated otherwise.

[0030] Unless otherwise indicated to the contrary, numerical values ​​should be understood to include numerical values ​​that are the same when reduced to the same significant figures, and numerical values ​​that differ from the stated value by less than experimental error using conventional measuring techniques of the type described herein to determine the numerical value.

[0031] All ranges disclosed herein are inclusive of the recited endpoints and are independent of the endpoints (e.g., "between 2 grams and 10 grams, and all intermediate values, includes 2 grams, 10 grams, and all intermediate values"). The endpoints of the ranges and any values ​​disclosed herein are not limited to the exact ranges or values, but are sufficiently imprecise to include values ​​that are close to these ranges and / or values. All ranges are combinable.

[0032] As used herein, approximation may be applied to modify any quantitative expression that may vary without resulting in a change in the basic function to which it is associated. Thus, a value modified by terms such as "about" or "substantially" may in some cases not be limited to the exact value specified. At least in some cases, an approximation may correspond to the precision of an instrument measuring the value. The modifier "about" should also be considered to disclose a range defined by the absolute values ​​of the two endpoints. For example, the phrase "about 2 to about 4" also discloses the range "2 to 4". The term "about" may refer to plus or minus 10% of the indicated numerical value. For example, "about 10%" may indicate a range of 9% to 11%, and "about 1" may mean 0.9 to 1.1. Other meanings of "about" are apparent from the context, such as rounding, so for example, "about 1" may also mean 0.5 to 1.4. Additionally, the term "comprising" should be understood to have the open-ended meaning of the term "including," but also includes the closed meaning of the term "consisting." For example, a composition comprising components A and B can be a composition comprising A, B, and other components, but can also be a composition consisting of only A and B. All documents cited herein are incorporated by reference in their entirety for all purposes.

[0033] TiO 2In all cases, 2D flakes were obtained, except when TMAH was used as the precursor. A typical cross-sectional scanning electron microscope (SEM) image of a TiC-derived film (Fig. 1b) clearly shows the two-dimensional nature of the FF. This micrograph is particularly clear in that it shows both undigested TiC particles (bottom right) and flakes. A colloidal suspension with a concentration of 10 g / L is shown in the inset of Fig. 1b. SEM images of the other films are shown in Fig. 5. The color of the FF varied from light gray to dark gray. The fact that these flakes can be synthesized from non-lamellar precursors, resulting in structurally and chemically similar FF, is strong evidence for a bottom-up approach. In our interpretation, TMAH acts as a nearly universal solvent that dissolves the precursor and releases Ti atoms that spontaneously react with C and O in TMAH / water to form 2D flakes consisting of self-assembled nanofilaments (see below). Thus, the role of TMAH is twofold: solvent and template former.

[0034] Ti after ethanol cleaning 3 AlC 2 The X-ray diffraction (XRD) pattern of the derived film (inset in Figure 2a) is typical of a 2D material. [7,9] The XRD patterns of the dried FF obtained from other precursors are shown in Figure 6. It is noteworthy that in most cases, there are no peaks related to the precursor. To get an idea of ​​the underlying structure, we obtained the XRD pattern (Figure 2a) of the vertically oriented FF.

[14] (see Figure 7a). This is because the Ti 3 AlC 2was obtained after heating at 50 °C for 3 days and washing with ethanol and water. The red vertical lines were obtained as follows: First, the c lattice constant LP was calculated from the horizontally aligned film (inset in Fig. 2a). Then, using the structure shown in Fig. 1c, the positions of all the peaks were calculated. All planes with non-zero l index were erased, leaving the red lines. The good agreement between the density functional theory (DFT) generated LP and the experimental LP (inset in Fig. 1d) confirms that we are dealing with a 4 Ti-layer anatase-based 2D material (see later). The patterns of other vertically aligned films obtained from other precursors are shown in Fig. 7b. In all cases, the same angle of the peak was obtained. This is extremely important and cannot be overemphasized, as it shows that the precursor chemistry does not change the formed structure, including the LP.

[0035] TiC, TiSiC 2 , and Ti 3 AlC 2 Transmission electron microscopy (TEM) images of the derived flakes revealed the presence of 2D flakes with lateral sizes >1 μm (Fig. 3a, Fig. 8). Selected area diffraction (SAD) of the latter in some areas resulted in three major rings (see insets in Fig. 8b and c). When the d-spacings of the rings were converted to 2θ values ​​(blue squares in Fig. 2a), they were found to match well with the XRD peaks, confirming that the SAD pattern is representative (see Table 3 for more detailed results). More interestingly, two sets of circular arcs (insets in Fig. 3a and Fig. 8a) were observed in other areas. One of the arcs indicates that the long axis of the nanofilaments is in the

[0110] direction, the other in the

[0200] direction. The angle between them is shown in both the inset and the main micrograph. These are in the same orientation as the frayed fibers seen at the edge of the sheet in the top left. The locations where the arcs were observed are limited. The regions where three rings are observed are more ubiquitous, suggesting the presence of small nfs oriented in all directions.Similarly, at this stage we cannot rule out the existence of truly amorphous regions.

[0036] Scanning transmission electron microscope (STEM) micrographs (Figure 3b) clearly show the fibrous nature of the sample. The width of the individual nanofilaments is estimated to be ≈1 nm. Their thickness is ≈5.9 Å, so that their cross-section is approximately 6x10 Å in size. 2 So we are dealing with nanofilaments with lengths on the order of micrometers (see the inset in Fig. 3b and Fig. 8c). Further TEM micrographs are shown in Fig. 8. The theoretical surface area of ​​these nanofilaments is ≈1500 m 2 Note that / g.

[0037] Figures 3c and 9 show TEM and atomic force microscopy (AFM) maps of a TiC-based sample spin-coated on glass (80 °C for 5 days, washed with water). The fibrous nature of the product and the tendency for self-alignment are evident. When the same suspension was diluted 500 times and drop-cast, individual nanofilaments separated (Figure 3d). The AFM trace along the blue line in Figure 3d shows that the minimum ribbon thickness or height is ≈1.5 nm (inset of Figure 3d).

[0038] To determine the number of Ti layers per filament, we predicted the LP using first-principles calculations. For this, we performed relaxation calculations for three supercell structures consisting of 2- (not shown), 4- (Fig. 1c), and 6-Ti layers (Fig. 10a), bounded at the top and bottom by the lowest-energy anatase (101) surface

[16] . (Note that our coordinate system differs from that of anatase; here the c-axis is the stacking direction, see the Crystallography section of SM). Next, we calculated the TiO 2-2x C x (x is 0.25 or Ti 4 O 6To obtain the overall chemical composition of α-α, two O atoms were replaced by one C atom at the slab center, taking into account the structural C and dynamically stabilizing the structure (Fig. 10b). All other configurations resulted in dynamic instability. As shown in the inset of Fig. 1d, the b-axis LPs of the three structures are in good agreement with the experimental values, especially considering that the DFT calculations were performed at 0 K. However, when the number of Ti layers is increased to 4 or 6, a large increase in the a-LP is observed, approaching the experimental value (blue curve in the inset of Fig. 1d). The thicknesses of the four- and six-layer anatase are ≈5.9 Å and ≈8 Å, respectively. The diameter of the TMA cation ranges from 4.5 to 6 Å [17,18]. Using the lower limit, the d-spacings between the filaments of the four- and six-layer structures are 10.4 Å and 12.5 Å, respectively. Using the upper limit, the d-spacing of a four-layer structure (11.9 Å) is obtained, which is in good agreement with the d-spacing of 11.5 obtained from XRD (Fig. 2a and inset of Fig. 6a). That is, the experimental value is consistent with a four-layer structure, and the six-layer structure is too thick.

[0039] Raman spectroscopy of many FFs (Figure 2b) shows that all peaks belong to anatase, regardless of the precursor chemistry.[15,19]

[0040] A comprehensive study by X-ray photoelectron spectroscopy (XPS) was performed to elucidate the chemical nature of the flakes (Figs. 11-13 and Table 4). The Ti and O bond energies were found to be a weak function of the precursor chemistry (Fig. 11), cleaning protocol, or heating to 800 °C in Ar (Fig. 12a), again confirming the chemical similarity of all the films. Further evidence for the bottom-up approach is the Ti-O bond energy, which exhibits a small Si peak. 3 Silicon Carbide 2 Except for the as-derived film, all other XPS spectra are composed of only three elements: Ti, C, and O, regardless of the starting precursor (Figure 13).

[0041] As discussed, it was not possible to quantify the C content in the flakes. EELS of some TiC-based flakes showed that the atomic ratio of Ti:C:O was ≈1:1:1 (Fig. 2c and Table 5). Small amounts of nitrogen were present in these flakes, but are ignored here for simplicity. It is important to note that EDS in both SEM and TEM confirmed that the Ti:O ratio was ≈1.0 (Table 6). Based on this ratio, if no C was present in the structure, the oxidation state of Ti must be ≈+2, which is supported by X-ray absorption near edge structure (XANES) measurements at the Ti K-edge of TiC-derived films (Fig. 2d) showing that the average oxidation state (AOS) is between +3 and +4. In all cases, the O:Ti ratio in XPS was closer to 3 than 1 (Table 7).

[0042] To better understand the chemical nature and flake morphology, thermogravimetric analysis (TGA) was performed on selected films up to 800 °C in Ar. The results are shown in Figure 14a. TiO 2 With the notable exception of the TiB-derived film, in all other cases, heating of the LiCl-washed films showed two major weight loss events, one before ≈200 °C and one at or above ≈300 °C. 2 , TiC and Ti 3 Silicon Carbide 2 The latter is much more rapid in the Ti-based films. In most cases, the weight loss at 300°C is about 4%. 3 AlC 2The weight loss above 300 °C for TiC and TiN-derived films is more diffuse, but still totals ≈4%. The sharpness of the weight loss at 300 °C can be seen well in Fig. 14b for the TiC film heated to 800 °C in air. In this experiment, the TGA was equipped with a mass spectrometer, and the results are shown in Fig. 14c. Water was the only gas evolved up to 400 °C. The first is probably weakly bound interlayer water, and the second could be hydration water bound to Li ions. The absence of high atomic number species indirectly proves that the LiCl cleaning step cleared the interlayer space of TMA cations and other reaction products. Not surprisingly, the weight loss of the film washed only with ethanol was larger (red curve in Fig. 14a).

[0043] After the TGA run, the XRD patterns of the resulting powders were obtained (Figure 15). Rietveld refinement of the XRD patterns gave the values ​​shown in Table 8. In all cases, two major phases were identified: lithium titanate, LT, phase-Li 1.33 Ti 1.67 O 4 and rutile or anatase. Ti 3 AlC 2 , Ti 3 Silicon Carbide 2 , TiC, TiO 2 / LTA molar ratio is ≈7:3; TiB 2 In the case of TiO, the ratio is close to 1:1; 2 In the case of , there is almost no LT. The higher the Li content, the more Ti in the film 3+ Therefore, our approach is suitable for Ti, which is considered in many applications. 3+ / Ti 4+ can be used to adjust the ratio.

[0044] Washing with ethanol alone and heating the film to 800 °C in Ar did not result in a Li-containing phase. Thus, the presence of the LT phase is due to the interlayer cations (TMA +, and / or protons) were exchanged for Li during the LiCl washing step, in a manner very reminiscent of the MXene studies.[20,21]TiO 2 The sample from was only slightly lithiated, even after washing with LiCl (Table 8). The TGA of this sample (black curve in Figure 14a) is also an outlier for the same reason. The cation exchange rules out the possibility that we are dealing with a layered double hydroxide. The absence of a Cl signal in the XPS (see Figure 13b) also supports this conclusion.

[0045] Based on the EELS, XANES, DFT and TGA results, the chemical nature of the flakes is Z δ (Ti 4+ ) 1-δ (Ti 3+ ) δ O 2-2x C x where it is reasonable to assume that x<1.0. Z is a cation that accounts for the oxidation state of Ti being <4+. Otherwise, the reduction in oxidation state must be balanced by cations. Note that this conclusion assumes that the nanofilaments are free of defects, a highly unlikely scenario. The fact that many of the films are dark grey to black strongly suggests the presence of defect states in the band gap.

[0046] The overall picture is more complex. For example, in some areas the Ti:X ratio (X=O+C+N) approaches 1 (see spots 1 and 5 in Table 5). We acknowledge here that we are dealing with a very complex system that is not necessarily homogeneous and will require a lot of work to decipher. Despite these comments, our conclusions regarding the structure of the flakes and the presence of C in the structure remain valid.

[0047] Before discussing the properties, it is useful to discuss the mechanism involved in the formation of the nanofilaments and 2D layers. Starting with tetra-n-butyl titanate and TMAH, Chen et al. concluded that the presence of TMAH provided organic cations to assist and direct the Ti-octahedra polycondensation process, resulting in the observed regular array of rectangular nanocrystalline anatase particles.

[15] Tan et al. 4 was hydrothermally treated at 125 °C.

[19] For reaction times of 1 and 4 h, their XRD patterns were the same as in Figure 2a, except for the position of (240) near 60° 2θ. Increasing the reaction time to 12 and 24 h transformed the 2D material into bulk anatase. They proposed a model in which TMAH helps assemble the Ti octahedra into 2D layers while simultaneously intercalating the resulting sheets. There is no reason to think that this mechanism would not apply here, except that our material does not transform into bulk anatase, since we are working at a low enough temperature for the TMA molecules to be more stable

[22] . Finally, unlike all previous studies, TMAH must not only cap the low-energy (00l) faces

[19] , but also the second face perpendicular to the growth direction. This creates a situation in which growth is limited to one dimension. Figure 3b and the inset in Figure 8f suggest that the filaments may be chemically "pulled" out of the precursor and the polycondensation process may occur at that interface (without being bound to any particular theory). Once the nanofilaments are formed, they need to self-assemble into 2D flakes. Figure 8d is a snapshot showing how the nanofilaments self-align to form "crystalline" regions in certain areas.

[0048] The films obtained from TiC and MAX phases were conductive, with conductivities in the range of 0.01–0.05 S / cm, whereas TiO 2 , TiB 2This is not the case for those obtained from . These conductivities are approximately 5-6 orders of magnitude lower than MXene, which is in the range of 2,000-25,000 S / cm, but clearly orders of magnitude higher than typical oxides, especially the common version of the layered titanate, namely lepidocrocite. [23-25] Conductivity is not always present, suggesting that there are unknown variables at work that are currently under investigation.

[0049] To clarify the electronic structure, UV-Vis absorption spectra were measured from 200 to 800 nm. The Tauc plots (Figure 4a) of all the films show an indirect band gap E g The indirect band gap is determined to be in the range of 4 eV, which is the highest reported value for anatase, but decreases with decreasing dimensions. g

[27] Liao et al.

[28] reported that E g We predicted and confirmed ≈3.6 eV. Our flakes are ≈6x10 Å 2 Because it is made up of nanofilaments, E g This record TiO 2 E g This value cannot be overemphasized because it indirectly confirms the extreme dimensions of our nanofilaments. At 3.3 eV, our TiO 2 Based on nanoparticles g is the E of bulk anatase as expected. g Note that the ΔE is close to ΔE (Figure 4a).

[0050] Interestingly (and without being bound to any particular theory or embodiment), the Ti concentration inferred from the Li concentration is 3+There is no correlation between Ti content and the Urbach tail as some have suggested

[29] . We therefore tentatively conclude that this tail and electrical conductivity are due to point defects. In some of the EELS measurements, the Ti fraction approaches 0.5 (Table 5), suggesting the formation of O / C vacancies. This comment aside, further work is needed to understand why some of these films can be conductive.

[0051] To explore potential applications, we explored the performance of our 2D flakes in lithium-ion batteries (LIBs) and lithium-sulfur batteries (Li-S). The results are shown in Figures 4b and c, respectively, and are promising in both cases. A detailed discussion is given in SM (see Figures 17 and 18). For LIBs, the absence of lithiation and delithiation peaks at 1.64 and 2.1 V (inset in Figure 4b) indicates that the electrode is a TiO 2 It was confirmed that the ZnO-based electrode was neither a ZnO-based nor a layered titanate [30, 31]. Furthermore, the coulombic efficiency of this electrode was ≈99.3% after 200 cycles (Figure 17d), reflecting highly efficient electrochemical cycling.

[0052] Lithium-sulfur (Li-S) coin cells with Li anodes and TiC-derived TCO cathodes were assembled and cycled, with the results shown in Figure 4c and detailed in SM.

[0053] These results are included to confirm the 2D nature of the obtained materials and their potential. However, these results can be greatly improved by a better understanding of what has been obtained. These comments aside, we acknowledge that more work is required to understand the mechanisms, involvement, etc., which is clearly beyond the scope of this paper. However, it goes without saying that these materials show great potential, especially as Li-S cathodes. For example, as shown in Figure 18b, the capacity was constant for about 300 cycles at ≈1000 mAh / g before fading.

[0054] Finally, to further demonstrate the versatility of TCOs, we explored their potential biomedical applications and found that they can indeed be used for cancer treatment (Figure 4d). Here, mouse 4T1 breast cancer cells and B16-F10 melanoma cells were treated with different concentrations of TiC-derived TCOs for 24 hours, after which their viability was measured using an MTT assay. At a concentration of 200 μg / ml, TCO particles were able to induce cancer cell death and were more effective in 4T1 breast cancer cells than in B16-F10 melanoma cells. Thus, a composition according to the present disclosure can be administered to a cancer-containing sample, and this administration can induce the death of cancer cells.

[0055] conclusion

[0056] We have discovered a simple, inexpensive, relatively high-yielding, near-ambient temperature, fully scalable, one-pot, bottom-up approach to fabricate 2D titanium carbo-oxide films composed of nanofilaments. By heating 11 different layered and non-layered titanium-based precursor powders in TMAH at different temperatures (25 °C–85 °C) for various times, we transformed 10 of them into anatase-based 2D flakes with substantial C content of ≈6x10 Å. 2 Some of the films were dark and conductive, with electrical conductivity in the range of 0.01–0.05 S / cm. However, the Urbach tail and the Ti content inferred from the overall Li content were not significant. 3+ Since no correlation was found between the percentage of , they concluded that the electrical conductivity is probably due to point defects rather than reduced oxidation states. TCOs have shown good performance as electrodes in LIBs and Li-S batteries, and may also have potential for biomedical applications.

[0057] Materials and Methods

[0058] Film Processing

[0059] The synthesis process involves immersing the precursor powder in 25 wt% TMAH in a polyethylene jar that is heated on a hot plate at temperatures ranging from room temperature (RT) to 85 °C for periods ranging from 24 hours to one week. After reaction with TMAH, (Ti 2 SbP, TiB 2 and TiO 2 A dark black precipitate (except for 1.0 μg / ml) was obtained, which was collected, washed with ethanol, shaken and centrifuged at 3500 rpm for multiple cycles until a clear supernatant was obtained. Once the supernatant was clear, 30 mL of deionized water was added to the washed product and shaken for 5 min. After centrifugation at 3500 rpm for 0.5 h without sonication, a stable colloidal suspension was obtained. Unreacted powder was precipitated. The colloid was then vacuum filtered to produce FF, a portion of which was characterized.

[0060] In some cases, an additional washing step with LiCl solution was performed and the resulting flakes were characterized. 5M LiCl solution was added to the black colloidal suspension obtained above. This resulted in deaggregation. The precipitate was shaken, centrifuged at 5000 rpm for three cycles, and washed with deionized water. The LiCl / deionized water washes were repeated until the pH was ≈ 7. The washed precipitate was then sonicated in a cold bath under flowing Ar for 1 h, shaken for 5 min, and centrifuged at 3500 rpm for 10 min. The colloidal suspension was filtered to obtain the FF. The FF was then dried overnight in a vacuum chamber before further characterization.

[0061] In a few cases, the black slurry produced from the reaction of TMAH and TiC was centrifuged (5000 rpm, 5 min) without adding any solvent, the supernatant was decanted, and the precipitate was suspended in 20 mL of deionized water, shaken for 5 min, and then centrifuged at 3500 rpm for 30 min. The resulting black colloidal suspension was used for XRD (not shown) and TEM examination.

[0062] The yield is expressed as the number of moles of Ti in the resulting anatase-like structure relative to the number of moles supplied from the precursor (for simplicity, TiO 2The molar masses of TiC and Ti are used as a ratio. 3 AlC 2 The yields for are 19% and 28%, respectively. Typically, the yields are on the order of ≈20%, depending on the starting precursor. The solids loading of the colloidal suspension is on the order of 10 g / L.

[0063] X-ray diffraction, XRD

[0064] XRD patterns of the air-dried samples were acquired using a powder diffractometer (Rigaku SmartLab) with Cu Kα radiation in the 2–65°2θ range, with a step size of 0.02° and a dwell time of 1 s / step in Bragg-Brentano geometry. XRD patterns of the vertically aligned films were also acquired in transmission mode.

[0065] Raman spectroscopy, RS

[0066] Raman scattering spectra were collected from a number of precursor FFs at 300 K in air (Figure 2b). The samples were probed with a 532-nm laser irradiated with 3.75 mW of power and focused to a spot diameter of ~0.5 μm. The scattered light was collected by geometric backscattering, dispersed and detected using a single-axis monochromator equipped with a charge-coupled detector array (Horiba XploRA, Edison NJ).

[0067] X-ray photoelectron spectroscopy, XPS

[0068] XPS was performed using a spectrometer (VersaProbe 5000, Physical Electronics, Chanhassen, MN). Monochromatic Al-Kα X-rays with a spot size of 200 μm were used. High-resolution spectra were collected with a pass energy of 23.5 eV, an energy step of 0.05 eV, and a step time of 0.5 s. Ten repetitions were performed per scan. XPS spectra were calibrated by setting the major CC peak at 285.0 eV. Peaks were fitted using an asymmetric Gaussian / Lorentzian line shape. Background was determined using the Shirley algorithm. All samples were mounted on the XPS stage with carbon tape.

[0069] Scanning Electron Microscope, SEM

[0070] Micrographs and elemental compositions were obtained using a SEM (Zeiss Supra 50 VP, Carl Zeiss SMT AG, Oberkochen, Germany) equipped with an energy dispersive X-ray spectrometer (EDS, Oxford EDS, Oxfordshire, UK). Reported EDS values ​​are the average of at least two measurements at low magnification on randomly selected areas at an accelerating voltage of 15 kV and a dwell time of 60 s.

[0071] Atomic Force Microscope, AFM

[0072] The thickness of the filaments and flakes was measured using an AFM (Multimode 8 AFM by Bruker Nano Surfaces). Peak force tapping AFM imaging mode was applied to obtain the surface morphology and height profile. Scans were performed using a ScanAsyst-Air silicon nitride probe at a scanning speed of 0.6 Hz. Topographic images were recorded with a resolution of 256*256 pixels and analyzed with Nano Scope Analysis software.

[0073] Transmission electron microscope, TEM

[0074] TEM imaging and electron diffraction patterns were collected using a JEOL JEM2100F field emission TEM. The TEM was operated at 200 keV with an image resolution of 0.2 nm. Images and diffraction patterns were collected with a Gatan USC1000 CCD camera. Scanning transmission electron microscopy (STEM) was performed on a monochromated and double Cs-corrected FEI Titan3 60-300 operating at 300 kV.

[0075] Electron Energy Loss Spectroscopy, EELS

[0076] STEM-EELS spectra were acquired using a Gatan GIF Quantum ERS post-column imaging filter with 0.25 eV / channel energy dispersion and a collection half angle of 55 mrad, averaging 100 spectra acquired every 1 s. Elemental quantification of the edges present was performed using the built-in functionality of Digital Micrograph.

[0077] X-ray absorption near edge structure, XANES

[0078] Ti K-edge isotropic XANES spectra were recorded at 54° from the film normal using circularly polarized X-rays provided by the first harmonic of a HELIOS-II helical undulator (HU-52). The X-ray beam was monochromated using a fixed exit double crystal monochromator with a pair of Si(111) crystals. The total fluorescence yield signal was collected by a Si photodiode mounted in backscattering geometry. The spectra were corrected for the effects of self-absorption. The samples were compressed powder pellets with a thickness of ≈1 mm. The isotropic XANES spectra were normalized to a unity edge jump far above the absorption edge. The photon energy scale was calibrated using the pre-peak maximum in the absorption spectrum of the Ti film set at 4965.6 eV. The spot size was 0.4x0.3 mm. 2 The experiment was carried out at the ID12 beamline of the European Synchrotron Radiation Facility (ESRF) in Grenoble.

[0079] Electrical resistivity

[0080] Electrical resistivity measurements were performed at room temperature using a four-point probe apparatus (Loresta-AX MCP-T370, Nitto Seiko, Japan) and converted to electrical conductivity values.

[0081] Thermogravimetric analysis, TGA

[0082] A thermobalance (TA Instruments Q50, New Castle, DE) was used for the TGA analysis. Small pieces of FF (≈20 mg) were placed in a sapphire crucible and heated to 800 °C at 10 °C / min while purging with Ar at 10 mL / min. In one experiment, a thermobalance attached to a mass spectrometer was used. These measurements used a thermoanalyzer (TA instruments, SDT 650, Discovery Series) coupled to a mass spectrometer (TA instruments Discovery Series) operating at an ionization potential of 40 V. The samples were held at room temperature for 0.5 h and then heated to 800 °C at a rate of 10 °C / min under a flow of dry compressed air at 50 mL / min. The carrier gas and evolved gas from the sample were measured by scanning the range from 1 to 100 atomic mass units. The ion current for each m / z (mass / charge ratio) was normalized to the initial sample weight.

[0083] UV-vis.

[0084] UV-VIS spectra were recorded using a spectrophotometer (Evolution 300 UV-Visible, Thermo Scientific). Measurements were performed in transmission mode on 1–10 μm thick films coated on quartz slides.

[0085] DFT calculation

[0086] First-principles calculations were performed using the Vienna ab initio simulation package (VASP).

[32] The projector augmented wave method (PAW) was used with a plane wave basis set extended to a kinetic energy cutoff of 600 eV. Exchange-correlation effects were described by the generalized gradient approximation using the Perdew, Burke, and Ernzerhof (PBE) functionals.

[33] Integration of the Brillouin zone was performed using the Gauss-smearing method with a smear width of 0.05 eV. The electronic configuration of the pseudopotential used was C:[He]2S. 2 2P 2 , O:[He]2s 2 2p 4 , Ti_sv:[Ne]3s 2 3p 6 3d 2 4s 2 The computational supercell was constructed using a slab model consisting of various anatase (101) atomic layers with periodicity along the a- and b-axes of the supercell. The geometry and atomic positions of the supercell were relaxed until the forces on each atom were <5 meV / Å. To eliminate interactions between the periodic images perpendicular to the slab, a vacuum region of 15 Å was added along the c-axis (new coordinate system) of the supercell. For the structure optimization, the first Brillouin zone had a 16x6x1 k-point sampling, and for the phonon calculation, a 8x3x1 supercell and 2x2x1 k-point sampling were used.

[0087] Electrochemical measurements

[0088] Lithium-ion battery, LIB

[0089] To evaluate the electrochemical performance of TCOs as electrode materials for LIB materials, the TCOs were tested in a half-cell configuration against Li metal. The TCA working electrode was fabricated by drop-casting a slurry of active material with binder and carbon additive onto a carbon-coated copper foil. The slurry was prepared by mixing 40.0 mg of active material, 5.0 mg of poly(vinylidene fluoride) (PVDF, Sigma Aldrich, USA) binder N-methyl-2-pyrrolidinone (NMP, 99.5%, Acros Organics, Extra Dry over Molecular Sieve, Germany) solvent, and 5.0 mg of carbon black. The prepared electrodes were dried at 60 °C overnight. The mass loading of the electrodes was ~1.2–1.5 mg / cm. 2 The two-electrode CR2032 coin cell was 2 and H 2 The device was assembled in an Ar-filled glove box with O<0.1 ppm. Li metal foil was used as the counter electrode. 1M LiPF in ethylene carbonate (EC) / ethyl methyl carbonate (EMC) 3:7 (weight ratio) 6 and glass fiber were used as the electrolyte and separator, respectively. The Li / Li + CV and galvanostatic charge-discharge tests were performed with a cutoff electrochemical voltage window of 0.001 to 3.0 V against the cathode. Electrochemical impedance spectroscopy measurements were performed with frequencies between 100 kHz and 10 mHz using an electrochemical workstation (BioLogic VMP3).

[0090] Lithium-sulfur battery

[0091] To evaluate the performance of TCO as a sulfur host in Li-S batteries, a slurry-based method was used to fabricate TCO / S cathodes. Briefly, a slurry was prepared by mixing 35 wt% vacuum-dried TCO, 35 wt% sulfur, S, 20 wt% conductive carbon (Alfa Aesar, Super P), and 10 wt% battery grade PVDF binder (MTI Corp.). The materials were manually ground with a mortar and pestle until the mixture was homogenous. N-methyl-2-pyrrolidone (TCI, USA) was then added slowly (~25 min) until the required visible viscosity and homogeneity of the slurry was achieved. The slurry was then cast onto aluminum foil at a thickness of 20 μm using a doctor blade (MTI Corp., USA). After casting, the slurry was kept in a closed fume hood for 2 h and then transferred to a vacuum oven and dried at 50 °C for 12 h.

[0092] The dried TCO / S cathode was cut into a disk shape using a hole punch (diameter 11 mm). The electrode was then weighed and placed in an Ar-filled glove box (MBraun Lab Star, O 2 <1 ppm, and H 2 The Li-S coin cells were assembled using a CR2032 (MTI Corporation and Xiamen TMAX Battery Equipment) coin-type Li-S cell with a TCO / S cathode, a 15.6 mm diameter, 450 μm thick Li disk anode (Xiamen TMAX Battery Equipment), a three-layer separator (Celgard 2325), a stainless steel spring and two spacers, and an electrolyte. The Li-S cell was fabricated using 1M LiTFSi and 1 wt% LiNO in a 1:1 volumetric mixture of 1,2-dimethoxyethane and 1,3-dioxolane. 3 The electrolyte was purchased from TMAX Battery Equipment, China, and according to the manufacturer, it contained traces of oxygen and moisture (H 2 O<6ppm and O 2<1 ppm). The assembled coin cells were rested at open circuit potential for 10 h before electrochemical experiments. Cyclic voltammetry was performed using a potentiostat (Biologic VMP3) at Li / Li + For voltages between 1.8 and 2.6 V, 0.1 mV.s -1 Long-term cycling stability tests were performed using a battery cycler (Neware BTS 4000) at various C rates (where 1C = 1675 mAh.g) between voltages of 1.8 and 2.6 V. -1 ) The Li-S cell was conditioned for 2 min. Cycles were performed at 0.1C and 0.2C, followed by an extended cycle at 0.5C.

[0093] Biological testing

[0094] One day before treatment, 4T1 and B16-F10 cells were plated at a density of 10,000 cells / well in 96-well plates. The cells were cultured at 37°C / 5% CO in RPMI-1640 medium supplemented with 10% fetal bovine serum and 100 IU / mL penicillin / streptomycin. 2 The cells were cultured for 24 h at 10 μg / mL, 50 μg / mL, or 200 μg / mL of TiC-based TCO. After 24 h of treatment, a thiazolyl blue tetrazolium bromide (MTT) assay was performed according to the manufacturer's protocol. The absorbance at 570 nm and 630 nm was measured. Relative cell viability was determined by comparing with the absorbance of untreated cells. All measurements were performed in triplicate. Data were analyzed using two-way ANOVA with Tukey's post-hoc test.

[0095] [1] KS Novoselov, et al., Science 353 (2016) 461.

[0096] [2] D. Deng, KS Novoselov, Q. Fu, N. Zheng, Z. Tian, ​​X. Bao, Nat. Nanotechnol. 11 (2016) 218-230.

[0097] [3] KS Novoselov, Science 306 (2004) 666-669.

[0098] [4] KS Novoselov, D. Jiang, F. Schedin, TJ Booth, VV Khotkevich, SV Morozov, AK Geim, PNAS 102 (2005) 10451-10453.

[0099] [5] F. Xia, H. Wang, Y. Jia, Nat. Common. 5 (2014) 4458-4458.

[0100] [6] M. Naguib, M. Kurtoglu, V. Presser, J. Lu, J. Niu, M. Heon, L. Hultman, Y. Gogotsi, MW Barsoum, Adv. Mater. 23 (2011) 4248-4253.

[0101] [7] L. Verger, C. Xu, V. Natu, H.-M. Cheng, W. Ren, MW Barsoum, Curr. Open. Solid State Mater. Ski. 23 (2019) 149-163.

[0102] [8] SL Swartzen-Allen, E. Matijevic, Chem. Rev. Fr. 74 (1974) 385-400.

[0103] [9] L. Verger, V. Natu, M. Carey, MW Barsoum, Trends Chem. 1 (2019) 656-669.

[0104]

[10] T. Yang, TT Song, M. Callsen, J. Zhou, J.W. Chai, Y.P. Feng, S.J. Wang, M. Yang, Adv. Mater. Interfaces 6 (2019) 1801160.

[0105]

[11] Z. Sun, T. Liao, Y. Dou, S.M. Hwang, M.-S. Park, L. Jiang, J.H. Kim, S.X. Dou, Nat. Common. 5 (2014) 3813.

[0106]

[12] J. Xuan, Z. Wang, Y. Chen, D. Liang, L. Cheng, X. Yang, Z. Liu, R. Ma, T. Sasaki, F. Geng, Angew. Fabric. (2016).

[0107]

[13] DN Miller, AK Azad, H. Delpouve, L. Quazuguel, J. Zhou, A. Sinha, P. Wormald, JTS Irvine, J. Mater. Fabric. A 4 (2016) 5730-5736.

[0108]

[14] M. Ghidiu, MW Barsoum, J. Amer. Mirror. Soc. 100 (2017) 5395-5399.

[0109]

[15] Yunxia Chen, Xin He, Xiujian Zhao, Qihua Yuan, X. Gu, J. Colloid Interface Sci. 310 (2007) 171-177.

[0110]

[16] Frederic Labat, Philippe Baranek, C. Adamo, J. Chem. Comput Theory. 4 (2008) 341-352.<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">

[0111] <h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">

[17] Z. Liu, K. Ooi, H. Kanoh, W. Tang, T. Tomida, Langmuir 16 (2000) 4154-4164.<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">

[0112] <h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">

[18] S. L. Brock, et al. , J. Phys. Chem. B 103 (1999) 7416-7428.<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">

[0113] <h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">

[19] Z. Tan, K. Sato, S. Ohara, Adv Powder Technol 26 (2015) 296-302.<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">

[0114] <h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">

[20] M. Ghidiu, J. Halim, S. Kota, D. Bish, Y. Gogotsi, M.W. Barsoum, Chem. Mater. 28 (2016) 3507-3514.<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">

[0115] <h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">

[21] L. Verger, V. Natu, M. Ghidiu, M. W. Barsoum, J. Phys. Chem. C 20044-20050(2019) 19725-19733.<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">

[0116] <h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">

[22] X. Dong, J. Tao, Y. Li, H. Zhu, Appl. Surf 256 (2010) 2532-2538.<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">

[0117] <h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">

[23] AD Dillon, MJ Ghidiu, AL Krick, J. Griggs, SJ May, Y. Gogotsi, MW Barsoum, AT Fafarman, Adv. Funct. Mater. 26 (2016) 4162-4168.<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr">

[0118] <h2 style=";text-align:left;direction:ltr">

[24] M. Ghidiu, MR Lukatskaya, M.-Q. Zhao, Y. Gogotsi, M.W. Barsoum, Nature (2014).

[0119]

[25] CJ Zhang, B. Anasori, A. Seral-Ascaso, S.-H. Park, N. McEvoy, A. Shmeliov, GS Duesberg, JN Coleman, Y. Gogotsi, V. Nicolosi, Adv. Mater. 29 (2017) 1702678.

[0120]

[26] P. Makula, M. Pacia, W. Macyk, J. Phys. Fabric. 9 (2018) 6814-6817.

[0121]

[27] ASD Wang, T. Sasaki, Chem. Rev. Fr. 114 (2014) 9455-9486.

[0122]

[28] T. Liao, Z. Sun, SX Dou, ACS Appl. Mater. Interfaces 9 (2017) 8255-8262.

[0123]

[29] D.-e. Gu, Y. Lu, B.-c. Yang, Y.-d. Hu, Chem. Common. (2008) 2453-2455.

[0124]

[30] Y. Dong, M. Yu, Z. Wang, Y. Liu, X. Wang, Z. Zhao, J. Qiu, Adv. Funct. Mater. 26 (2016) 7590-7598.

[0125]

[31] J. Xu, C. Jia, B. Cao, W. Zhang, Electrochim. Acta 52 (2007) 8044-8047.

[0126]

[32] G. Kresse, J. Furthmuller, Phys. Rev. B 54 (1996) 11169-11186.

[0127]

[33] JP Perdew, K. Burke, M. Ernzerhof, Phys. Rev. Lett. 77 (1996) 3865-3868.

[0128] Supplemental Disclosures

[0129] Reasons for LiCl Cleaning

[0130] Based on previous studies on ion exchange and colloidal stability of 2D materials [1-9], a LiCl washing step was performed for the following reasons:

[0131] To remove the TMA cations from between the layers, which was useful because in some cases the TMA cations formed a non-conductive film.

[0132] To prove the existence of exchangeable cations between the layers. If there are no exchangeable cations, Li + No ions would have been intercalated between the layers.

[0133] After heating the filtered film FF to 800 °C in Ar, the percentage of the crystalline phase obtained was determined by the Ti 3+ It was possible to estimate the content of

[0134] X-ray diffraction

[0135] Not surprisingly, X-ray diffraction, XRD, of the horizontally aligned film failed to reveal its underlying structure. Instead, a pattern of vertically aligned films was obtained using a setup similar to that of Ghidiu et al.

[10] . To obtain the films, 1–3 ml of the colloidal suspension was drop-cast using a pipette onto a Kapton tape attached to a glass slide (inset in Fig. 7a). Three layers of the colloidal suspension were drop-cast and dried between applications. Drying was performed at room temperature, RT, in a Petri dish using a fan. The drop-cast sample was fixed onto a vertical sample holder using double-sided tape (Fig. 7a). The sample holder was then aligned to maximize the signal through the sample.

[0136] Crystallography

[0137] Please note that the coordinate system used here is not that of bulk anatase but that shown in the bottom left of Fig. 1c. Following our recipe, the grown nfs-based 2D flakes will preferentially orient along the (110) plane, which is the lowest energy plane in bulk anatase (i.e., the anatase coordinate system). To be consistent with the 2D literature, in our system the stacking direction of the flakes is along the c-axis, i.e., in our coordinate system this is the (00l) plane.

[0138] Transmission electron microscope, TEM

[0139] TEM images show that only a small proportion of the regions are aligned. A significant proportion of the nanofilaments are not aligned and are randomly oriented in the plane of the flakes. This is also confirmed by selected area diffraction patterns (SAD), where diffraction rings are visible in most flakes.

[0140] Electron Energy Loss Spectroscopy, EELS

[0141] EELS spectra of five types of particles were measured for TiC-based flakes heated at 50 °C in TMAOH for 3 days and then washed with ethanol. Figure 2c includes the carbon-K edge at an energy loss of ~280 eV, the titanium-L3,2 peak at an energy loss of ~450 eV, and the oxygen-K edge at an energy loss of ~530 eV. All spectra are normalized to the peak intensity of the titanium edge. The thicker particles show a steeper background, which is more easily seen at the lower energies of the spectrum. The top and bottom spectra are clearly less intense compared to the middle three particles. Of the five particles, the top and bottom spectra contain approximately the same amount of C, while the chemical composition of the middle three (2, 3, and 4) is consistent with a Ti:C:O atomic ratio of ≈1:1:1. All spectra also show a small amount of NK (not shown) at an energy loss of ~400 eV. In this paper, we ignore this small amount of N. The results of these spectra are summarized in Table 5. Since the intensity of the C-loss peak did not change with time under electron beam irradiation, it is assumed that C is in the backbone of the structure.

[0142] Importantly, two particles contained a significantly higher proportion of Ti - in one case the atomic fraction of Ti was close to 0.5 - suggesting that the Ti atoms were chemically reduced to an average oxidation state of +2 during the process.

[0143] It should be noted here that the intensity of the various peaks did not change upon prolonged illumination under the beam, so the C is presumed to originate from within the structure, and could otherwise originate from a contaminated sample. Heating to 500 °C in the TEM chamber did not change the Ti / C ratio.

[0144] X-ray absorption near edge structure, XANES,

[0145] XANES experiments were performed at the Ti K-edge of Ti-derived films at the ESRF beamline ID12. XANES spectra at the K-edge of transition metals are dominated by dipolar transitions to unoccupied 4p states, usually accompanied by a structured pre-edge peak associated with transitions to 4p-3d hybridized states.

[11] The energy position of the absorption edge, and especially the pre-edge peak, is generally associated with the oxidation state and coordination of the absorbing atom. We have compared the XANES spectrum of our TCO film (Figure 2d) with that of Ti. 4+ (anatase), TiC, Ti 3 AlC 2 and Ti 3+ (TiCl 3 ), we find that the average Ti oxidation state of the TCO film is between 3+ and 4+. These results clearly indicate that our material is not pure anatase, i.e., C-free anatase.

[0146] Both covalent bonds and 3d counting can lead to an energy shift in the K-edge XANES spectrum of Ti. The former mechanism is mainly manifested at the main edge. However, the energy position of the weaker features below the main edge (arising from the quadrupolar transition 1s->3d) is dominated by the effect of 3d occupancy. Comparing the first derivatives of the XANES spectra in the energy range from 4964 eV to 4968 eV (inset in Fig. 2d), the oxidation state of Ti in TiC is significantly higher than that of the reference compound TiCl. 3 It is clear that TiCO is close to 3+ as TiCO. 3+ and Ti 4+ The differential spectrum contains two peaks, and the energy positions of these peaks are the same as those of TiCl. 3 Peak and TiO 2 This coincides with the first peak of

[0147] X-ray photoelectron spectroscopy, XPS

[0148] Typical XPS spectra of all the films are compared in Figure 11. The peaks were fitted and the results are summarized in Table 4. The Ti:O ratios of the films are summarized in Table 7. The latter was determined from the areas of the Ti peak at ≈459 eV and the O peak at ≈530 eV. The ratio is approximately 1:3.

[0149] The C 1s spectrum (second row in Figure 11) has three peaks, the largest of which is centered at a binding energy (BE) of ≈285 eV, and two smaller peaks at ≈286.5 eV and 288.5 eV. These are consistent with the commonly reported CC, C-OH, and -COOH BEs in the literature, respectively.

[12] We recently showed that in MXenes, the BE is 282 eV when the C atom is surrounded by six Ti atoms.

[13] Here, no peak is seen at 282 eV, consistent with C not being surrounded by six Ti atoms. In our structures, C is bound to four Ti atoms, so it is not surprising that their BE is higher than 282 eV. After careful consideration, we conclude that the C peaks in our TCOs overlap with the fortuitous CC peaks.

[0150] As shown in Figure 11, Ti 2p 3 / 2 The BE of is a weak function of treatment. For example, the BE after ethanol washing, LiCl treatment, and even TGA treatment up to 800 °C are all similar, and therefore the values ​​obtained for these films can be considered representative of all BEs at all processing conditions. Heating the films in air shifted the XPS spectra (not shown).

[0151] Figure 13 shows the Ti signal where the Si signal was observed. 3 Silicon Carbide 2 Except for the case of (Fig. 13c), all other films show that they are composed of only the three elements Ti, O, and C. In addition, there is no Cl between the layers, confirming that we are not dealing with a bilayer hydroxide (Fig. 13b).

[0152] Thermogravimetric analysis, TGA

[0153] The sample was washed with ethanol and LiCl and placed in the TGA and heated to 800 °C in Ar. The results are shown in Figure 14. 2 With the notable exception of the LiCl-washed and TiC-derived films (two outliers in Figure 14a), the overall weight loss was about 15%. The LiCl-washed TiC-derived films were run once in Ar, giving the same results as when heated in Ar, except in this case the TGA was connected to a mass spectrometer, which showed that the only gas evolved up to 400 °C was water (Figures 14b and c). Above that temperature, some CO 2 occurred.

[0154] TiO 2 is an outlier because XRD and TEM (Fig. 16) show that in this case it is not 2D structures that form, but nanoanatase particles. At this point it is instructive to compare the XRD diffraction patterns of anatase and our 2D flakes. In the latter, the (104) and (105) peaks are absent, and the 63°2θ peak of anatase is shifted much closer to 60°2θ (Fig. 16a).

[0155] Rietveld analysis of a sample heated to 800°C in a TGA

[0156] The results of Rietveld analysis (RA) of the XRD patterns of FF heated to 800 °C in Ar in TGA (Figure 15) were cut out and the fractions of various phases were quantified. The results are shown in Table 8. In most cases, the phases obtained were lithium titanate, LTA, Li 1.33 Ti 1.66 O 4 and anatase or rutile, TiO 2 Most of the χ 2 The value of is <2, and the fit is very good. 2 Note that the film obtained from is not layered and therefore has the lowest LTA volume fraction.

[0157] Atomic Force Microscope, AFM

[0158] To better understand the dimensions and organization of the 2D flakes, AFM studies of the 2D flakes and nanoribbons were performed, and the results shown in Figure 3 c and d confirm that the obtained 2D flakes are composed of self-aligned nanofilaments.

[0159] To obtain nanofilaments, TiC powder was heated in TMAH at 80 °C for 5 days. The colloidal suspension was spin-coated on a glass slide at 1000 rpm for 10 s, and an unmistakable fibrous structure was observed by AFM, with the filaments aligned in roughly the same direction (Figure 3c). The colloidal suspension was then diluted 500 times and drop-cast onto a substrate, resulting in detached filaments (Figure 3d). By tracing the AFM across the blue line shown in Figure 3d, the resulting profile indicated that the thickness of the thinnest fiber was ≈1.5 nm (inset of Figure 3d).

[0160] Lithium-ion battery, LIB

[0161] For the lithium-ion secondary battery, a CR2032 coin cell was prepared and Ti 3 AlC 2 The electrochemical performance of the derived electrodes was investigated. + In the voltage range of 0.1mVs -1 The cyclic voltammetry (CV) curves obtained at a scan rate of 1000 s (inset in Figure 4b) are very similar to those in the literature for MXene. [14,15]

[0162] Figure 4b in this paper shows a specific current of 20 mAg -1 The galvanostatic charge / discharge voltage profile for the initial lithiation specific capacity is 714mAhg and the initial delithiation specific capacity is 265mAhg. -1 The specific capacity loss during the first lithiation process is attributed to the formation of a solid electrolyte interphase (SEI) layer below 0.85 V and other irreversible reactions.

[16] The specific capacity stabilizes after two cycles. The stable lithiation specific capacity is 210 mAhg and the delithiation specific capacity is 209 mAhg. -1is maintained after five cycles. Figure 17a plots the electrochemical impedance spectroscopy of the electrode, showing low system resistance (4 Ω) and small charge transfer resistance (18 Ω), confirming the observed electrochemical performance. The rate capacity results are shown in Figure 17b. -1 So, ~110mAhg -1 It can maintain a reversible capacity of 1000mAg. -1 But, ~80mAhg -1 A reversible capacity of 20mAg can be achieved. -1 When switched back to , the capacity is ~180mAhg -1 As shown in Figure 17c and d, the as-prepared TCO electrode recovered to 100 mAg -1 The electrode showed excellent cycle stability performance with a specific current of 155 mAhg at 200 cycles. -1 Furthermore, the coulombic efficiency of this electrode was ≈98.9% after 30 cycles, reflecting highly efficient electrochemical cycling.

[0163] Lithium sulfur, Li-S electrode

[0164] Figure 18a shows the 0.1mV-s -1 At a scan rate of 1.8 to 2.6 V (vs. Li / Li + ) range. The CV curve shows two sharp and distinct cathodic peaks and one anodic peak. The first cathodic peak at 2.3 V is due to the reduction of S to long-chain lithium polysulfides (LiPs) (12), and the second peak is due to the subsequent reduction of Li from LiPs. 2 6 / Li 2 The peak shift after the first anodic peak is attributed to the nucleation / reorganization during the redeposition of LiP to 12. Figure 4c shows a typical discharge plateau, which is consistent with the CV results. The TCO / S composite electrode discharged 1300, 1200, and 1050 mAhg at 0.1, 0.2, and 0.5 C rates, respectively. -1Such a high capacity may be related to the electrical conductivity of TiCO in combination with surface active sites that could bind LiP. To evaluate the long-term stability of the cathode, -2 The cell was cycled at 0.5C with a S load of 1.0 μA. Figure 14b shows that the initial capacity of the cell was ~1300 mAhg. -1 After the first 5 cycles, it was ~1000mAhg -1 This initial capacity loss is associated with two conditioning cycles at low rates of 0.1°C and 0.2°C. The composite reaches a capacity of ~1000mAhg after ≈300 cycles. -1 The cathode exhibited a capacity of 100% retention, with the capacity declining after 300 cycles. These values ​​are impressive considering that the cathode was made of TCO flakes and commercial S powder mixed into a slurry using a mortar and pestle.

[0165] Mesoscopic Materials

[0166] 50g TiB 2 The powder was placed in 500 mL of 25% TMAH solution and heated at 80° C. for 3 days in a polyethylene bottle and shaken on a mechanical lab shaker. After 3 days on the shaker, the resulting suspension was allowed to settle and the liquid was decanted. 500 mL of ethanol was then added, the suspension was allowed to settle, and the liquid was decanted. The ethanol wash was repeated a total of three times.

[0167] After decanting the supernatant, the resulting precipitate was washed with 500 mL of 5 M LiCl aqueous solution for 4 h at room temperature. After a second water wash, the supernatant was decanted to obtain a grey precipitate. This precipitate was dried overnight at 40 °C and then manually ground to a fine powder.

[0168] The XRD pattern of the powder showed a low angle peak with d-spacing of 9.4A, and non-basal peaks at 25° and 48° corresponding to 2D anatase. The (104) and (105) peaks had disappeared. Some low intensity peaks belonging to unreacted TiB2 precursor remained. SEM micrographs of the resulting powder (Figure 19) showed a uniform distribution of well separated mesoporous particles with sizes of approximately 10 μm. Mesoporous particles can be composed of ligaments with lengths of several microns and diameters of 100 nm or less. Mesoporous particles can be used, for example, in drug delivery, energy storage, devices, etc. As an example, therapeutic agents can be attached to mesoporous particles (e.g., adsorption, intercalation, etc.), and the therapeutic agent-attached particles can be introduced to a subject, allowing the therapeutic agent to be delivered to the subject.

[0169] References and Notes

[0170] [1] AP Ferris, WB Jepson, J. Colloid Interface Sci. 51 (1975) 245-259.

[0171] [2] M. Ghidiu, J. Halim, S. Kota, D. Bish, Y. Gogotsi, MW Barsoum, Chem.Mater.28 (2016) 3507-3514.

[0172] [3] M. Ghidiu, S. Kota, J. Halim, AW Sherwood, N. Nedfors, J. Rosen, VN Mochalin, MW Barsoum, Chem.Mater.29 (2017) 1099-1106.

[0173] [4] WG Lawrence, J. Am.Ceram 41 (1958) 136-140.

[0174] [5] L. Verger, V. Natu, M. Ghidiu, MW Barsoum, J. Phys. Chem.C 20044–20050(2019) 19725–19733.

[0175] [6] MM Gudarzi, Langmuir 32 (2016) 5058-5068.

[0176] [7] G. Lagaly, S. Ziesmer, J. Colloid Interface Sci. 100–102 (2003) 105–128.

[0177] [8] T. Missana, A. Adell, J. Colloid Interface Sci. 230 (2000) 150–156.

[0178] [9] V. Natu, M. Sokol, L. Verger, MW Barsoum, J. Phys. Chem.C 122 (2018) 27745–27753.

[0179]

[10] M. Ghidiu, MW Barsoum, J. Amer.Ceram.Soc. 100 (2017) 5395–5399.

[0180]

[11] A. Rogalev, F. Wilhelm, Phys. Met.Metallogr. Rev. 116 (2015) 1285–1

[0181]

[12] TL Barr, S. Seal, J. Vac.Sci. Technol 13 (1995) 1239–1246.

[0182]

[13] V. Natu, M. Benchakar, C. Canaff, A. Habrioux, S. Celerier, MW Barsoum, Matter 4 (2021) 1224-1251.

[0183]

[14] J. Luo, X. Tao, J. Zhang, Y. Xia, H. Huang, L. Zhang, Y. Gan, C. Liang, W. Zhang, ACS Nano 10 (2016) 2491-2499.

[0184]

[15] B. Ahmed, DH Anjum, MN Hedhili, Y. Gogotsi, HN Alshareef, Nanoscale 8 (2016) 7580-7587.

[0185]

[16] M. Naguib, J. Come, B. Dyatkin, V. Presser, P.-L. Taberna, P. Simon, MW Barsoum, Y. Gogotsi, Electrochem. commun.16 (2012) 61-64.

[0186]

[17] A. Manthiram, Y. Fu, S.-H.Chung, C. Zu, Y.-S.Su, Chem.Rev. 114 (2014) 11751-11787.

[0187] Aspects

[0188] The following aspects are illustrative, and do not limit the scope of the disclosure or the appended claims.

[0189] Aspect 1. A composition comprising a plurality of oxide-based nanofilaments and / or sub-nanofilaments, and optionally an amount of carbon. (As described herein, the nanofilaments can comprise titanium.) The composition can exist as a mesoporous powder, in which the powder particulates comprise the oxide-based nanofilaments and / or sub-nanofilaments.

[0190] Embodiment 2. The composition of embodiment 1, wherein at least some of said nanofilaments and / or sub-nanofilaments have a width in the range of about 3 to about 50 Å. The width can be, for example, about 3 to about 50 Å, about 5 to about 45 Å, about 7 to about 40 Å, about 9 to about 35 Å, about 12 to about 30 Å, about 15 to about 20 Å, and all intermediate values ​​and combinations.

[0191] The composition can be configured in a suspension, such as a solution, or in an ink, which can be printed. With respect to the ink, the ink can be sprayed, printed, or otherwise applied to the substrate. The ink can include a solvent, a binder, and the like.

[0192] Embodiment 3. The composition of embodiment 2, wherein at least a portion of the nanofilaments and / or sub-nanofilaments have an average width in the range of from about 7 to about 20 Å.

[0193] Embodiment 4. The composition of any one of embodiments 1-3, wherein the nanofilaments and / or sub-nanofilaments define a non-circular cross-section.

[0194] Embodiment 5. The composition of embodiment 4, wherein said nanofilaments and / or subnanofilaments define a cross-sectional aspect ratio of greater than 1 to about 10. For example, the cross-sectional aspect ratio can be 1.1 to 10, 1.5 to 9, 1.8 to 8, 2.2 to 7, 2.5 to 6, 2.8 to 5, or even 3.2 to 4.

[0195] Embodiment 6. The composition of embodiment 5, wherein said nanofilaments and / or sub-nanofilaments define a cross-sectional aspect ratio of from about 2 to about 5.

[0196] Aspect 7. The composition of any one of aspects 1-6, wherein the nanofilaments and / or sub-nanofilaments are from about 10 to about 100 Å. 2 For example, the average cross-sectional area is in the range of about 10 to about 100 Å. 2, about 15 to about 90 Å 2 , about 20 to about 80 Å 2 , about 30~70Å 2 , about 40 to about 60 Å 2 , or about 50 Å 2 The range may be:

[0197] Aspect 8. The composition according to any one of Aspects 1 to 7, wherein at least a portion of the nanofilaments and / or sub-nanofilaments have a length in the range of from about 1 nm to about 25 μm. The length can be, for example, from about 1 nm to about 25 μm, from about 10 nm to about 20 μm, from about 50 nm to about 10 μm, from about 100 nm to about 5 μm, or from about 250 nm to about 2 μm.

[0198] Embodiment 9. The composition of embodiment 8, wherein at least some of the nanofilaments and / or sub-nanofilaments have a length in the range of from 1 nm to about 1 μm.

[0199] Aspect 10. The composition of any one of aspects 1-9, wherein the nanofilaments and / or sub-nanofilaments are comprised of a plurality of flakes; and the nanofilaments and / or sub-nanofilaments can self-assemble into flakes. Without being bound to a particular theory or embodiment, the nanofilaments and / or sub-nanofilaments can be aligned in a plane; and the flakes can include two or more layers of aligned nanofilaments and / or sub-nanofilaments, thereby providing flakes that are an ordered stack of nanofilament and / or sub-nanofilament layers. The nanofilaments can be self-aligned.

[0200] Aspect 11. The composition of aspect 7, wherein at least a portion of the flakes are in a common plane. The flakes can be well stacked along the stacking direction. The nanofilaments and / or sub-nanofilaments can result in a typical XRD pattern of a 2D material, i.e., an XRD pattern in which only one family of planes diffracts. Without being bound to a particular theory or embodiment, the nanofilaments and / or sub-nanofilaments can self-assemble into 2D flakes.

[0201] Embodiment 12. The composition according to any one of embodiments 1 to 11, further comprising a pharma- ceutically acceptable carrier.

[0202] Embodiment 13. The composition of any one of embodiments 1-12, further comprising one or more materials that are lethal to cancer cells.

[0203] Embodiment 14. The composition of any one of embodiments 1-13, further comprising a binder. Such a binder can be, for example, an adhesive, a pressure sensitive adhesive, or other matrix material.

[0204] Example 15. The composition of example 14, wherein the binder comprises a polymer.

[0205] Aspect 16. The composition of any one of aspects 1-15, wherein the nanofilaments and / or sub-nanofilaments exhibit an XRD pattern exhibiting reduced (104) and (105) peaks at about 38° and about 55° two theta (2θ) compared to the XRD pattern of nano or bulk anatase. The disclosed nanofilaments and / or sub-nanofilaments can, in some embodiments, exhibit Raman spectra very similar to those of bulk anatase, but can differ from bulk anatase with respect to their XRD spectra, as described herein.

[0206] Embodiment 17. A device, said device comprising a composition according to any one of embodiments 1 to 16.

[0207] Embodiment 18. The device of embodiment 17, wherein the device comprises an electrode.

[0208] Aspect 19. The device of aspect 17, wherein the device is characterized as an energy storage device. Such devices can be, for example, batteries, supercapacitors, etc. The devices can be rechargeable, but also disposable. Such devices can be comprised of mobile computing devices, mobile communication devices, computing devices, lighting devices, signal transmitting devices, and signal receiving devices.

[0209] Embodiment 20. The device of embodiment 18, wherein the electrode comprises the composition of any one of embodiments 1-16.

[0210] Embodiment 21. The device of embodiment 17, wherein the device comprises a dispenser, the dispenser having disposed therein a composition according to any one of embodiments 1-16. The dispenser may be, for example, a syringe, a nozzle, or the like. Such a dispenser may be used to deliver a composition (e.g., according to any one of embodiments 1-16) to a subject (e.g., a human patient) and / or a sample obtained from the patient. Such a sample may be, for example, a blood sample.

[0211] A method comprising the step of operating the apparatus of embodiment 17.

[0212] Aspect 23. A method comprising contacting a mono-, binary, ternary, or higher carbide, nitride, boride, phosphide, aluminide, or silicide, or titanium metal, with a quaternary ammonium salt and / or a base, wherein the mono-, binary, ternary, or higher carbide, nitride, boride, phosphide, aluminide, or silicide, or titanium metal, is optionally water insoluble, and the water insoluble binary, ternary, or higher carbide, nitride, boride, phosphide, aluminide, or silicide optionally comprises a transition metal, and the transition metal optionally comprises titanium, and wherein the contacting is performed under conditions sufficient to produce nanofilamentary (and / or sub-nanofilamentary) products, which are capable of self-organizing into 2D flakes.

[0213] Exemplary carbides include, for example, titanium carbide, zirconium carbide, hafnium carbide, vanadium carbide, niobium carbide, tantalum carbide, chromium carbide, molybdenum carbide, tungsten carbide, and iron carbide. Exemplary nitrides include, for example, aluminum nitride, boron nitride, calcium nitride, cerium nitride, europium nitride, gallium nitride, indium nitride, lanthanum nitride, lithium nitride, magnesium nitride, niobium nitride, silicon nitride, strontium nitride, tantalum nitride, titanium nitride, vanadium nitride, zinc nitride, and zirconium nitride.

[0214] Examples of borides include, for example, aluminum diboride, aluminum dodecaboride, aluminum magnesium boride, barium boride, calcium hexaboride, cerium hexaboride, chromium (III) boride, cobalt boride, dinikel boride, erbium hexaboride, erbium tetraboride, hafnium diboride, iron boride, iron tetraboride, lanthanum hexaboride, magnesium diboride, nickel boride, niobium diboride, osmium boride, plutonium boride, rhenium diboride, ruthenium boride, samarium hexaboride, scandium dodecaboride, silicon boride, strontium hexaboride, tantalum boride, titanium diboride, trinickel boride, tungsten boride, uranium diboride, yttrium boride, zirconium diboride, and the like.

[0215] Examples of phosphides include, for example, aluminum gallium phosphide, aluminum gallium phosphide, aluminum phosphide, bismuth phosphide, boron phosphide, cadmium phosphide, calcium monophosphide, calcium phosphide, carbon monophosphide, cobalt (II) phosphide, copper (I) phosphide, dysprosium phosphide, erbium phosphide, europium (III) phosphide, ferrophosphorus, gadolinium phosphide, gallium arsenide phosphide, gallium indium arsenide antimony phosphide, gallium phosphide, holmium phosphide, ... Indium gallium arsenide phosphide, indium gallium phosphide, indium phosphide, iron phosphide, lanthanum phosphide, lithium phosphide, lutetium phosphide, neodymium phosphide, niobium phosphide, phosphorus carbide, phosphorus chloride, silicide phosphide, plutonium phosphide, praseodymium phosphide, samarium phosphide, scandium phosphide, sodium phosphide, strontium phosphide, telluride phosphide, terbium phosphide, thulium phosphide, titanium(III) phosphide, uranium monophosphide, ytterbium phosphide, yttrium phosphide, zinc diphosphide, zinc cadmium arsenic phosphide, and zinc phosphide.

[0216] Examples of aluminides include, for example, magnesium aluminide, titanium aluminide, iron aluminide, and nickel aluminide.

[0217] Examples of silicides include, for example, nickel silicide, sodium silicide, magnesium silicide, platinum silicide, titanium silicide, tungsten silicide, and molybdenum silicide.

[0218] Without being bound to any particular theory or embodiment, titanium-containing mono-, bi-, or ternary or higher carbides, nitrides, borides, phosphides, aluminides, or silicides are particularly preferred. Similarly, titanium sponge is believed to be a particularly preferred form of titanium metal for use in the disclosed technology. For example, titanium sponge can be contacted with a quaternary ammonium salt as described herein to produce a nanofilamentary (or sub-nanofilamentary) product as described herein.

[0219] Aspect 24. The method of aspect 23, wherein the conditions include a temperature of 0 to 100°C, 200°C, or 300°C for about 0.5 hours to about 1, 2, 3, 4, or 5 weeks. The temperature can be constant during the exposure time, or can be varied, e.g., increased and / or decreased. The temperature can be, for example, about 0 to about 300°C, about 5 to about 95°C, about 10 to about 90°C, about 15 to about 85°C, about 20 to about 80°C, about 25 to about 75°C, about 30 to about 70°C, about 35 to about 65°C, about 40 to about 60°C, about 45 to about 55°C, or about 50°C. Temperatures of 100 to 200°C are also suitable. The temperature can be varied during the exposure (e.g., exposure to a first temperature followed by exposure to a second temperature), but this is not a requirement. Exposure can be according to a preprogrammed schedule that sets, for example, the temperature and / or exposure time. The exposure temperature can be, for example, about 25°C, about 30°C, about 35°C, about 40°C, about 45°C, about 50°C, about 55°C, about 60°C, about 65°C, about 70°C, about 75°C, about 80°C, about 90°C, about 95°C, or about 100°C.

[0220] The conditions, in some embodiments, include a temperature of about 20 to about 300°C and an exposure time of about 0.5 hours to about 2, 3, 4, or 5 weeks. The conditions may include a temperature of about 100 to about 200°C and an exposure time of about 1 hour to about 1 week. The temperature may be constant during the exposure time, but may also be varied, e.g., increased and / or decreased. The temperature may be, for example, about 100 to about 200°C, about 105 to about 195°C, about 100 to about 190°C, about 115 to about 185°C, about 120 to about 180°C, about 25 to about 175°C, about 130 to about 170°C, about 135 to about 165°C, about 140 to about 160°C, about 145 to about 155°C, or about 150°C. The temperature may be varied during the exposure (e.g., exposure to a first temperature followed by exposure to a second temperature), but this is not a requirement. The exposure can be performed according to a pre-programmed schedule, for example, setting the temperature and / or exposure time. The exposure temperature can be, for example, about 125, about 130, about 135, about 140, about 145, about 150, about 155, about 160, about 165, about 170, about 175, about 180, about 190, about 195. The method can be performed in a closed system, for example, in a pressure vessel. The pressure can be atmospheric, but can also be below atmospheric pressure or above atmospheric pressure, for example, greater than 1 atmosphere (101.325 kPa) to about 10 atmospheres (1013.250 kPa).

[0221] The exposure period (which may be referred to as the "reaction time") may be, for example, from about 1 hour to about 7 days, from about 5 hours to about 6 days, from about 15 hours to about 5 days, from about 20 hours to about 4 days, from about 24 hours to about 3 days, or from about 2 days. However, as some examples, the exposure may be from 12 hours to about 72 hours, from about 15 hours to about 70 hours, from about 18 hours to about 64 hours, from about 24 hours to about 60 hours, from about 30 hours to about 55 hours, from about 33 hours to about 52 hours, from about 37 hours to about 48 hours, from about 40 hours to about 45 hours, and all intermediate values ​​and subcombinations of the ranges.

[0222] Example 25. The method of example 23, comprising contacting a mono-, bi-, ternary, or more boride (which may include Ti) with a quaternary ammonium salt and / or a base to produce a product, which may be nanofilamentary and / or sub-nanofilamentary.

[0223] Example 26. The method of example 25, wherein the binary borides comprise one or more titanium borides.

[0224] Embodiment 27. The method of any one of embodiments 23-26, wherein the quaternary ammonium salt and / or base comprises ammonium hydroxide, ammonium halide, or any combination thereof.

[0225] Aspect 28. The method of aspect 27, wherein the quaternary ammonium hydroxide is selected from the group consisting of tetramethylammonium hydroxide (TMAOH), tetraethylammonium hydroxide (TEAOH), tetrapropylammonium hydroxide (TPAOH), tetrabutylammonium hydroxide (TBAOH), ammonium hydroxide (NH 4 OH), their amine derivatives, or any combination thereof.

[0226] Aspect 29. The method of aspect 27, wherein the quaternary ammonium salt comprises a quaternary ammonium chloride, a quaternary ammonium bromide, a quaternary ammonium iodide, a quaternary ammonium fluoride, or any combination thereof. It should be understood that either or both of the quaternary ammonium salt and the quaternary ammonium base can be used.

[0227] Embodiment 30. The method of any one of embodiments 23 to 29, further comprising filtering the product.

[0228] Embodiment 31. The method of any one of embodiments 23-30, further comprising washing the product with a metal salt and / or other water-soluble metal compound.

[0229] The metal salt can be a metal halide salt, such as a Li halide, a Na halide, a K halide, a Rb halide, a Cs halide, a Fr halide, a Be halide, a Mg halide, a Ca halide, a Sr halide, a Ba halide, a Ra halide, a Mn halide, a Fe halide, a Ni halide, a Co halide, a Cu halide, a Zn halide, a Mo halide, a Nb halide, a W halide, or any combination thereof.

[0230] Example 32. The method of any one of Examples 23-31, further comprising washing the product with the metal salt and / or a water-soluble metal compound. The metal salt can optionally comprise a metal sulfate, nitrate, chromate, acetate, carbonate, permanganate, or metal hydroxide, or any combination thereof.

[0231] Aspect 33. The method of aspect 32, wherein the metal in the salt can be essentially any metal from the periodic table. However, as some non-limiting examples, the metal in the metal salt can be Li, Na, K, Cs, Mg, Ca, Cr, Mn, Fe, Co, Ni, Cu, Zn, Nb, Mo, Cd, Ta, or W, or any combination thereof. The metal salt can be, for example, LiCl, KCl, NaCl, LiF, KF, NaF, LiOH, KOH, NaOH, or any combination thereof.

[0232] Example 34. The method of any one of Examples 32-33, wherein the metal salt is LiCl, KCl, NaCl, LiF, CsCl, KF, NaF, LiOH, KOH, NaOH, or any combination thereof.

[0233] Aspect 35. The method of any one of aspects 32-33, wherein the metal salt is CrCl 3 , MnCl 2 , FeCl 2 , FeCl 3 , CoCl2 , NiCl 2 , MoCl 5 , FeSO 4 , (NH 4 ) 2 Fe(SO 4 ) 2 , CuCl 2 , CuCl, ZnCl 2 or any combination thereof.

[0234] Aspect 36. The method according to any one of aspects 23 to 35, wherein the product is a composition according to any one of aspects 1 to 16.

[0235] Example 37. The method of any one of Examples 23-36, wherein the nanofilamentary (and / or sub-nanofilamentary) products exhibit XRD patterns exhibiting reduced (104) and (105) peaks at about 38° and about 55° two-theta (2θ) compared to the XRD patterns of nano or bulk anatase. As described elsewhere herein, the disclosed nanofilaments and / or sub-nanofilaments can, in some embodiments, exhibit Raman spectra similar to those of bulk anatase, but can differ from bulk anatase with respect to XRD spectra, as described herein.

[0236] Aspect 38. A method, comprising:

[0237] Particulate TiO 2 with a quaternary ammonium salt and / or a base,

[0238] the contacting step being carried out under conditions sufficient to produce an anatase nanoparticle product;

[0239] The nanoparticle product optionally has at least some nanoparticles having a diameter of from about 2 nm to about 1000 nm, optionally from about 10 nm to about 100 nm.

[0240] The nanoparticle product can be further processed, e.g., by heating, further reaction, etc. Further processing can be carried out to coarsen the product, e.g., to produce larger sized particles, e.g., about 0.1 to about 0.7 μm, or about 0.2 to about 0.5 μm.

[0241] The disclosed method for producing the anatase product of the present disclosure comprises the steps of: 2 (Pigment grade TiO 2 and providing an alternative to such TiO 2 , especially pigment grade TiO 2 The present invention provides an improvement over existing processes for manufacturing

[0242] More specifically, currently, pigment-grade TiO 2 To produce it, low-grade TiO 2 Starting with the low-grade TiO 2 is chlorinated at high temperature to give TiO 2 TiCl 4 and oxidizing the latter. The disclosed method is an improvement over this cumbersome existing process.

[0243] The contacting step can be carried out at about 20° C. to about 80° C., or about 25° C. to about 75° C., or about 30° C. to about 70° C., or about 35° C. to about 65° C., or about 40° C. to about 60° C., or about 45° C. to about 55° C., or even about 50° C. The contacting step can be carried out for, for example, about 5 minutes to about 5 hours, about 10 minutes to about 4.5 hours, about 15 minutes to about 4 hours, about 20 minutes to about 3.5 hours, about 30 minutes to about 3 hours, about 45 minutes to about 2 hours, or any combination or subrange thereof.

[0244] Example 39. The method of example 38, wherein the quaternary ammonium salt and / or base comprises ammonium hydroxide, ammonium halide, or any combination thereof.

[0245] Aspect 40. The method of aspect 38, wherein the quaternary ammonium base is selected from the group consisting of tetramethylammonium hydroxide (TMAOH), tetraethylammonium hydroxide (TEAOH), tetrapropylammonium hydroxide (TPAOH), tetrabutylammonium hydroxide (TBAOH), ammonium hydroxide (NH 4 OH), their amine derivatives, or any combination thereof.

[0246] Embodiment 41 The method of embodiment 38, wherein the quaternary ammonium salt comprises a quaternary ammonium chloride, a quaternary ammonium bromide, a quaternary ammonium iodide, a quaternary ammonium fluoride, or any combination thereof. Either or both of the quaternary ammonium salt and the quaternary ammonium base can be used, as described elsewhere herein.

[0247] Embodiment 42. The method of any one of embodiments 38 to 41, further comprising filtering the product.

[0248] Embodiment 43. A composition comprising a population of anatase nanoparticles produced according to any one of embodiments 38 to 42. Such nanoparticles can be in the size range of about 200 nm to about 600 nm, e.g., about 200 nm to about 600 nm, about 225 nm to about 575 nm, about 250 nm to about 550 nm, about 275 nm to about 525 nm, about 300 nm to about 500 nm, about 325 nm to about 475 nm, about 350 nm to about 450 nm, about 375 nm to about 425 nm, or even about 400 nm.

[0249] Embodiment 44. A TiO nanoparticle population produced according to any one of embodiments 38 to 42. 2 For example, the conventional TiO 2 with anatase nanoparticles according to the present disclosure, e.g., according to any one of embodiments 38 to 42, thereby replacing conventional TiO 2 It is possible to incorporate pigments which are usually manufactured by

[0250] Embodiment 45. A method comprising the step of contacting a mono-, binary, ternary, or more carbide, nitride, boride, phosphide, aluminide, or silicide, or titanium metal, with a quaternary ammonium salt and / or a base, wherein the mono-, binary, ternary, or more carbide, nitride, boride, phosphide, aluminide, or silicide, or titanium metal is optionally water insoluble, and the water insoluble binary, ternary, or more carbide, nitride, boride, phosphide, aluminide, or silicide optionally comprises a transition metal, which optionally comprises titanium, wherein the contacting is optionally performed with shaking, and wherein the contacting is performed under conditions sufficient to produce mesoporous particles.

[0251] Embodiment 46. A method comprising contacting a mono-, binary, ternary, or more carbide, nitride, boride, phosphide, aluminide, or silicide, or titanium metal with a quaternary ammonium salt and / or a base, wherein the mono-, binary, ternary, or more carbide, nitride, boride, phosphide, aluminide, or silicide, or titanium metal is optionally water insoluble, and the water insoluble binary, ternary, or more carbide, nitride, boride, phosphide, aluminide, or silicide optionally comprises a transition metal, and the transition metal optionally comprises titanium, wherein the contacting is optionally performed with shaking, and wherein the contacting is followed by washing with at least one salt and is performed under conditions sufficient to produce mesoporous particles.

[0252] Embodiment 47. A method, the method comprising contacting a mono-, binary, ternary, or more carbide, nitride, boride, phosphide, aluminide, or silicide, or titanium metal, with a quaternary ammonium salt and / or a base, wherein the mono-, binary, ternary, or more carbide, nitride, boride, phosphide, aluminide, or silicide, or titanium metal, is optionally water insoluble, and the water insoluble binary, ternary, or more carbide, nitride, boride, phosphide, aluminide, or silicide optionally comprises a transition metal, the transition metal optionally comprises titanium, the contacting step being performed at a temperature of about 50 to about 95° C., optionally with shaking, followed by washing with LiCl to produce mesoporous particles.

[0253] Embodiment 48. A composition comprising mesoporous particles produced according to any one of claims 45-47.

[0254] The mesoporous particles can exhibit XRD patterns that exhibit reduced (104) and (105) peaks at about 38° and about 55° two theta (2θ) when compared to the XRD patterns of nano or bulk anatase. The disclosed mesoporous particles can, in some embodiments, exhibit Raman spectra very similar to those of bulk anatase, but can also differ from bulk anatase in terms of their XRD spectra, as described herein.

[0255] Aspect 49. A composition comprising mesoporous particles, the mesoporous particles comprising titanium, the mesoporous particles exhibiting an XRD pattern exhibiting reduced (104) and (105) peaks at about 38° and about 55° two theta (2θ) compared to the XRD pattern of nanoanatase or bulk anatase. The disclosed mesoporous particles, in some embodiments, can exhibit Raman spectra very similar to those of bulk anatase, but can also differ from bulk anatase in terms of their XRD spectra, as described herein.

[0256] Embodiment 50. The composition of any one of claims 48-49, further comprising a therapeutic agent.

[0257] Aspect 51. A method comprising delivering a therapeutic agent to a subject, the therapeutic agent being contained in a composition according to any one of claims 48-49.

[0258] Embodiment 52. An electrode, comprising the composition of any one of claims 48-49.

[0259] Embodiment 53. A device, said device comprising a composition according to any one of claims 48-49.

[0260] Aspect 54. The device of claim 52, wherein the device is an energy storage device.

[0261] Embodiment 55. A method comprising the step of operating an apparatus according to any one of claims 52-53.

Claims

1. A composition comprising a plurality of metal oxide sub-nanofilaments and / or nanofilaments, and optionally an amount of carbon.

2. The composition of claim 1, wherein at least a portion of the nanofilaments and / or sub-nanofilaments have a width in the range of about 3 to about 50 Å.

3. 10. The composition of claim 1, wherein: (a) the nanofilaments and / or sub-nanofilaments define a non-circular cross-section; (b) the nanofilaments and / or sub-nanofilaments define a cross-sectional aspect ratio greater than 1 and up to about 10; or (c) the nanofilaments and / or sub-nanofilaments have an average cross-sectional area in the range of about 10 to about 100 Å 2 .

4. The composition of claim 1, wherein at least a portion of the nanofilaments and / or sub-nanofilaments have a length in the range of 1 nm to about 25 μm.

5. The composition of claim 1, further comprising a pharma- ceutically acceptable carrier.

6. 10. The composition of claim 1, further comprising one or more substances that are lethal to cancer cells.

7. A device comprising the composition of claim 1.

8. The device of claim 7 , wherein the device comprises an electrode.

9. 1. A method, comprising: contacting a mono-, bi-, ternary or more carbide, nitride, boride, phosphide, aluminide, or silicide, or titanium metal, with a quaternary ammonium salt and / or a base; the mono-, bi-, ternary, or higher carbide, nitride, boride, phosphide, aluminide, or silicide, or titanium metal, is optionally water insoluble; said water insoluble binary, ternary or higher carbide, nitride, boride, phosphide, aluminide or silicide optionally comprising a transition metal, said transition metal optionally comprising titanium; The contacting step is carried out under conditions sufficient to produce a nanofilamentary product. method.

10. 10. The method of claim 9, wherein the conditions comprise a temperature of 0 to 100° C. for about 5 hours to about 1 week.

11. 10. The method of claim 9, wherein the quaternary ammonium salt and / or base comprises ammonium hydroxide, ammonium halide, or any combination thereof.

12. 10. The method of claim 9 further comprising washing the product with metal salts and / or other water-soluble metal compounds.

13. 1. A method, comprising: Particulate TiO 2 with a quaternary ammonium salt and / or a base; the contacting step is carried out under conditions sufficient to produce a nanoparticle product; The nanoparticle product optionally has at least some nanoparticles having a diameter of about 2 nm to about 1000 nm, optionally about 10 to about 100 nm. method.

14. 1. A method, comprising: contacting a mono-, bi-, ternary or more carbide, nitride, boride, phosphide, aluminide, or silicide, or titanium metal, with a quaternary ammonium salt and / or a base; the mono-, bi-, ternary, or higher carbide, nitride, boride, phosphide, aluminide, or silicide, or titanium metal, is optionally water insoluble; said water insoluble binary, ternary or higher carbide, nitride, boride, phosphide, aluminide or silicide optionally comprising a transition metal, said transition metal optionally comprising titanium; The contacting step is optionally performed with shaking; and The contacting step is carried out under conditions sufficient to produce mesoporous particles. method.

15. A composition comprising mesoporous particles produced according to claim 14.